Resin composition

By using resin compositions of epoxy resin, organic solvent and inorganic filler materials, the problems of nozzle clogging and resin separation in the slit coating method are solved, and high-quality insulating layer formation and thin film coating effects are achieved.

CN119220149APending Publication Date: 2024-12-31AJINOMOTO CO INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410846198.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-06-26
Filing Date
2024-06-27
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

In the slit type coating method, the drying of the nozzle leads to clogging problems, and the resin is poorly separated when a low-boiling solvent is used, and the solubility is reduced when a high-boiling solvent is used, which affects the coating effect and film formation.

Method used

Using a resin composition containing epoxy resin, organic solvent and inorganic filler material, ensure that the boiling point of the organic solvent is less than 100°C, the aromatic solvent content is more than 35%, and the viscosity is within the range of 3mPa·s to 5,000mPa·s, and the narrowness is achieved. The seam coating method forms a coating film and heat cures it.

Benefits of technology

The nozzle blockage and poor resin separation are effectively suppressed, the dryness and film formation after coating are improved, and excellent insulating layer formation is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004915752540000331
    Figure BDA0004915752540000331
Patent Text Reader

Abstract

The present invention addresses the problem of providing a resin composition which can suppress poor resin separation accompanying the low solubility of a resin, can suppress nozzle clogging caused by nozzle drying, and can suppress coating film depression defects after coating, and which has excellent thin film formability. [Solution] A resin composition containing (A) an epoxy resin, (B) an organic solvent, and (C) an inorganic filler, the content of the organic solvent having a boiling point of less than 100 DEG C in the component (B) being 5-60 mass% when the total amount of the component (B) is 100 mass%, and the content of the organic solvent having a boiling point of less than 100 DEG C in the component (B) being 5-60 mass% when the total amount of the component (B) is 100 mass%. The content of the aromatic solvent in the component (B) is 35 mass% or more, and the viscosity of the resin composition measured using an E-type viscometer at 25 DEG C and 50 rpm is 3-5,000 mPa.s.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a resin composition comprising an epoxy resin. Background Art

[0002] As a manufacturing technology for printed wiring boards, a manufacturing method based on a build-up method in which insulating layers and conductive layers are alternately stacked is known. In the manufacturing method based on the build-up method, a resin composition is generally cured to form an insulating layer.

[0003] Various methods are known as methods for forming an insulating layer, among which a slit coating method is advantageous in some aspects.

[0004] For example, the slit coating method can be applied with a small amount of coating liquid, which is conducive to reducing costs. The amount of coating liquid required for the slit coating method can be about 1 / 5 to 1 / 10 compared with the spin coating method. In addition, there is no particular limitation on the slit nozzle used in the coating, and slit nozzles sold by many manufacturers can be used.

[0005] In the curtain coating method, the solvent evaporates when the coating liquid comes into contact with the atmosphere, so that the viscosity changes and the thickness of the formed film changes. However, in the slit coating method, the coating liquid is a closed system before being discharged from the nozzle, so there is no viscosity change and a uniform film thickness can be formed.

[0006] In addition, there is a problem of resin seepage in the lamination method, and in the spin coating method, since the substrate (wafer) end is covered with resin, it is necessary to clean the end, and there is a problem of the coating liquid infiltrating (penetrating) into the cross section of the substrate in the curtain coating method. On the other hand, since the coating width can be controlled in the slit coating method, there will be no seepage, and it is not necessary to apply the coating to the end. In addition, it is also possible to apply the coating to the substrate end without the coating liquid infiltrating into the cross section.

[0007] Prior art literature Patent Literature Patent Document 1: Japanese Patent No. 6658514 Patent Document 2: Japanese Patent Application Publication No. 2021-157085 Patent Document 3: Japanese Patent Application Publication No. 2020-050854 Patent Document 4: Japanese Patent No. 6844636 Summary of the invention

[0008] Technical problem to be solved by the invention It should be noted that when the resin composition is applied to form an insulating layer, the occurrence of nozzle clogging due to the drying of the nozzle in the coating device such as a slit coater becomes a problem. In particular, when the boiling point of the solvent used is low, there is a tendency for clogging to occur easily. On the contrary, when the boiling point of the solvent used is high, the clogging of the nozzle can be suppressed, but the solubility of the resin becomes low, sometimes resulting in poor resin separation, and poor drying after coating.

[0009] In addition, when using a resin composition containing an inorganic filler, the adjustment of viscosity becomes a problem. For example, in the case of high viscosity, it is difficult to discharge from the slit, and the uniformity of the film thickness also deteriorates, so there is a tendency for the film formability to decrease. On the other hand, in the case of low viscosity, it is possible to produce a coating film depression (defective hajiki).

[0010] The present invention aims to provide a resin composition which can suppress poor resin separation due to low solubility of the resin, can suppress nozzle clogging due to nozzle drying, and can suppress coating film depression after coating and has excellent thin film formability.

[0011] Means of solving technical problems In order to achieve the subject of the present invention, the present inventors have conducted intensive studies on solvents, viscosity, etc., and as a result, found that the following resin composition unexpectedly can suppress poor resin separation associated with low solubility of the resin and can suppress nozzle clogging caused by nozzle drying. On the other hand, it can suppress poor coating film depression after coating and has excellent film formability; the resin composition comprises (A) an epoxy resin, (B) an organic solvent and (C) an inorganic filler, the content of the organic solvent having a boiling point of less than 100° C. in the component (B) is 5% to 60% by mass when the total component (B) (the total amount of the component (B)) is 100% by mass, the content of the aromatic solvent in the component (B) is 35% by mass or more when the total component (B) is 100% by mass, and the viscosity of the resin composition measured by an E-type viscometer at 25° C. and 50 rpm is 3 mPa·s to 5,000 mPa·s, thereby completing the present invention.

[0012] That is, the present invention includes the following contents. [1] A resin composition comprising (A) an epoxy resin, (B) an organic solvent, and (C) an inorganic filler, wherein: When the total amount of component (B) is set to 100 mass%, the content of the organic solvent with a boiling point of less than 100° C. in component (B) is 5 mass% to 60 mass%, and when the total amount of component (B) is set to 100 mass%, the content of the aromatic solvent in component (B) is 35 mass% or more, the viscosity of the resin composition measured using an E-type viscometer at 25° C. and 50 rpm is 3 mPa·s to 5,000 mPa·s, and the resin composition is used to form a coating film by coating on a substrate by roll coating, spray coating, spin coating, bar coating, slit coating, curtain coating or dip coating, and the coating film is thermally cured to form an insulating layer. [2] The resin composition according to [1] above, wherein the resin composition is applied onto a substrate by a slit coating method to form a coating film, and the coating film is thermally cured to form an insulating layer. [3] The resin composition according to [1] above, wherein the content of the component (C) is 85% by mass or less when the total amount of components other than the component (B) in the resin composition is 100% by mass. [4] The resin composition according to [1] above, wherein the content of the component (C) is 60% by mass or more when the total amount of components other than the component (B) in the resin composition is 100% by mass. [5] The resin composition according to [1] above, wherein the content of the aromatic solvent in the component (B) is 85% by mass or less when the total amount of the component (B) is 100% by mass. [6] The resin composition according to [1] above, wherein the content of the organic solvent having a boiling point of 130° C. or higher in the component (B) is 25% to 90% by mass when the total amount of the component (B) is 100% by mass. [7] The resin composition according to [1] above, wherein the content of the organic solvent having a boiling point of 100° C. or higher and less than 130° C. in the component (B) is 1% by mass to 20% by mass, when the total amount of the component (B) is 100% by mass. [8] The resin composition according to [1] above, wherein the content of the organic solvent having a boiling point of 100° C. or higher and lower than 130° C. in the component (B) is 5% by mass or higher, when the total amount of the component (B) is 100% by mass. [9] The resin composition according to [1] above, wherein the content of the non-aromatic solvent having a boiling point of 130° C. or higher in the component (B) is 10% by mass or less when the total amount of the component (B) is 100% by mass.

[10] The resin composition according to [1] above, wherein the content of the aromatic solvent having a boiling point of 130° C. or higher in the component (B) is 20% by mass or more, when the total amount of the component (B) is 100% by mass.

[11] The resin composition according to the above [1], wherein, when the total amount of the aromatic solvent (total aromatic solvent) is set to 100 mass%, the content of the aromatic solvent having a boiling point of 130° C. or higher in the aromatic solvent is 60 mass% or more.

[12] The resin composition according to [1] above, wherein the component (B) comprises a C9 aromatic hydrocarbon and a C 10 Aromatic solvents among aromatic hydrocarbons.

[13] The resin composition according to the above [1], wherein, when the total amount of the component (B) is set to 100% by mass, the content of the organic solvent formed by constituent atoms selected from carbon atoms, oxygen atoms and hydrogen atoms in the organic solvent (B) is 98% by mass or more.

[14] The resin composition according to [1] above, wherein the content of the component (B) is 15% to 50% by mass when all components in the resin composition are taken as 100% by mass.

[15] The resin composition according to [1] above, wherein the content of the radical polymerizable compound is 0% to 2% by mass when the total amount of components other than component (B) in the resin composition is 100% by mass.

[16] The resin composition according to [1] above, wherein the viscosity measured using an E-type viscometer at 25° C. and 50 rpm is 50 mPa·s to 1,500 mPa·s.

[17] The resin composition according to [1] above, wherein a thixotropic ratio calculated by dividing the viscosity measured at 25°C and 5 rpm using an E-type viscometer by the viscosity measured at 25°C and 50 rpm using an E-type viscometer is 1.00 to 1.50.

[18] The resin composition according to [1] above, wherein the thixotropic ratio calculated by dividing the viscosity measured at 25°C and 5 rpm using an E-type viscometer by the viscosity measured at 25°C and 50 rpm using an E-type viscometer is 1.00 to 1.15.

[19] A printed wiring board comprising an insulating layer formed from a cured product of the resin composition according to any one of [1] to

[18] above.

[20] A semiconductor device comprising the printed wiring board described in

[19] above.

[21] A method for producing a printed wiring board, wherein the method uses a resin composition having the following characteristics: comprising (A) epoxy resin, (B) organic solvent and (C) inorganic filler material, When the total amount of the component (B) is 100% by mass, the content of the organic solvent having a boiling point of less than 100° C. in the component (B) is 5% by mass to 60% by mass, when the total amount of the component (B) is 100% by mass, the content of the aromatic solvent in the component (B) is 35% by mass or more, and the viscosity measured using an E-type viscometer at 25° C. and 50 rpm is 3 mPa·s to 5,000 mPa·s; The method for manufacturing the printed wiring board comprises the following steps (1) to (3): (1) A step of applying the resin composition onto a substrate by a slit coating method to form a coating film (2) A step of vacuum drying the coating film and / or drying the coating film at a temperature of 50° C. or higher and less than 150° C. (3) A step of thermally curing the coating film at a temperature of 150° C. to 240° C. to form an insulating layer. Effects of the Invention

[0013] According to the present invention, a resin composition is provided which can suppress poor resin separation due to low solubility of the resin and nozzle clogging due to nozzle drying, and can suppress coating film depression after coating and has excellent thin film formability. DETAILED DESCRIPTION

[0014] Hereinafter, the present invention will be described in detail based on its preferred embodiments. However, the present invention is not limited to the following embodiments and examples, and can be implemented with arbitrary changes within the scope of the claims and their equivalents.

[0015] The resin composition of the present invention is a resin composition that is applied on a substrate to form a coating film by roller coating, spray coating, spin coating, bar coating, slit coating, curtain coating or dip coating (slit coating is preferred), and the coating film is thermally cured to form an insulating layer.

[0016] The resin composition of the present invention comprises (A) an epoxy resin, (B) an organic solvent and (C) an inorganic filler, wherein the content of the organic solvent having a boiling point of less than 100° C. in the component (B) is 5% to 60% by mass when the total amount of the component (B) is 100% by mass, the content of the aromatic solvent in the component (B) is 35% by mass or more when the total amount of the component (B) is 100% by mass, and the viscosity measured by an E-type viscometer at 25° C. and 50 rpm is 3 mPa·s to 5,000 mPa·s. Such a resin composition can suppress poor resin separation due to low solubility of the resin and can suppress nozzle clogging due to nozzle drying, and on the other hand, can suppress poor film depression after coating, and has excellent thin film forming properties.

[0017] The resin composition of the present invention may further include (D) a curing agent, (E) a thermoplastic resin, (F) a curing accelerator, and (G) other additives in addition to (A) an epoxy resin, (B) an organic solvent, and (C) an inorganic filler. Hereinafter, each component contained in the resin composition of the present invention will be described in detail.

[0018] <(A) Epoxy resin> The resin composition of the present invention contains (A) an epoxy resin. (A) The epoxy resin is a curable resin having an epoxy group.

[0019] Examples of the epoxy resin (A) include bixylenol epoxy resins, bisphenol A epoxy resins, bisphenol F epoxy resins, bisphenol S epoxy resins, bisphenol AF epoxy resins, dicyclopentadiene epoxy resins, trisphenol epoxy resins, naphthol novolac epoxy resins, phenol novolac epoxy resins, tert-butyl-catechol epoxy resins, naphthalene epoxy resins, naphthol epoxy resins, anthracene epoxy resins, glycidylamine epoxy resins, glycidyl ester epoxy resins, cresol epoxy resins, and the like. Novolac type epoxy resin, phenol aralkyl type epoxy resin, biphenyl type epoxy resin, linear aliphatic epoxy resin, epoxy resin having a butadiene structure, alicyclic epoxy resin, heterocyclic epoxy resin, spiro ring-containing epoxy resin, cyclohexane type epoxy resin, cyclohexanedimethanol type epoxy resin, naphthylene ether type epoxy resin, trimethylol type epoxy resin, tetraphenylethane type epoxy resin, isocyanurate type epoxy resin, phenolphthalimidine type epoxy resin, etc. (A) The epoxy resin may be used alone or in combination of two or more.

[0020] In the resin composition of the present invention, as (A) epoxy resin, it is preferred to include an epoxy resin having two or more epoxy groups in one molecule. The proportion of the epoxy resin having two or more epoxy groups in one molecule is preferably 50% by mass or more, more preferably 60% by mass or more, and particularly preferably 70% by mass or more relative to 100% by mass of the epoxy resin (A).

[0021] The epoxy resin includes an epoxy resin that is liquid at a temperature of 20° C. (hereinafter sometimes referred to as “liquid epoxy resin”) and an epoxy resin that is solid at a temperature of 20° C. (hereinafter sometimes referred to as “solid epoxy resin”). In the resin composition of the present invention, as the epoxy resin, only a liquid epoxy resin may be included, or only a solid epoxy resin may be included, or both a liquid epoxy resin and a solid epoxy resin may be included, but preferably both a liquid epoxy resin and a solid epoxy resin are included.

[0022] As the liquid epoxy resin, a liquid epoxy resin having two or more epoxy groups in one molecule is preferred.

[0023] As the liquid epoxy resin, preferred are glycirol type epoxy resin, bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol AF type epoxy resin, naphthalene type epoxy resin, glycidyl ester type epoxy resin, glycidyl amine type epoxy resin, phenol novolac type epoxy resin, alicyclic epoxy resin having an ester skeleton, cyclohexanedimethanol type epoxy resin, cyclic aliphatic glycidyl ether, and epoxy resin having a butadiene structure.

[0024] Specific examples of liquid epoxy resins include "EX-992L" manufactured by Nagase ChemteX, "YX7400" manufactured by Mitsubishi Chemical Corporation, "HP4032", "HP4032D", and "HP4032SS" (naphthalene-based epoxy resins) manufactured by DIC Corporation; "828US", "828EL", "825", and "EPIKOTE "828EL" (bisphenol A type epoxy resin); "jER807", "1750" (bisphenol F type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "jER152" (phenol novolac type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "630", "630LSD", "604" (glycidylamine type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "ED-523T" (glycirol type epoxy resin) manufactured by ADEKA Corporation; "EP-3950L", "EP-3980S" (glycidylamine type epoxy resin) manufactured by ADEKA Corporation; "EP-4088S" (dicyclopentadiene type epoxy resin) manufactured by ADEKA Corporation; "ZX1059" (a mixture of bisphenol A type epoxy resin and bisphenol F type epoxy resin) manufactured by Nippon Steel Chemical Materials Co., Ltd.; "EX-721" (glycidyl ester type epoxy resin) manufactured by Nagase ChemteX Corporation; "EX-991L" manufactured by ChemteX (an epoxy resin containing an alkylene oxide skeleton and a butadiene skeleton); "CELLOXIDE 2021P" manufactured by Daicel Corporation (an alicyclic epoxy resin with an ester skeleton); "PB-3600" manufactured by Daicel Corporation, "JP-100", "JP-200", and "JP-400" manufactured by Nippon Soda Co., Ltd. (epoxy resins with a butadiene structure); "ZX1658" and "ZX1658GS" manufactured by Nippon Steel Chemical Materials Co., Ltd. (liquid 1,4-glycidylcyclohexane type epoxy resins); "EG-280" manufactured by Osaka Gas Chemical Co., Ltd. (an epoxy resin containing a fluorene structure); "EX-201" manufactured by Nagase ChemteX (cyclic aliphatic glycidyl ether), etc.

[0025] As the solid epoxy resin, a solid epoxy resin having three or more epoxy groups in one molecule is preferred, and an aromatic solid epoxy resin having three or more epoxy groups in one molecule is more preferred.

[0026] As the solid epoxy resin, preferred are biphenylol type epoxy resin, naphthalene type epoxy resin, naphthalene type tetrafunctional epoxy resin, naphthol novolac type epoxy resin, cresol novolac type epoxy resin, dicyclopentadiene type epoxy resin, trisphenol type epoxy resin, naphthol type epoxy resin, biphenyl type epoxy resin, naphthylene ether type epoxy resin, anthracene type epoxy resin, bisphenol A type epoxy resin, bisphenol AF type epoxy resin, phenol aralkyl type epoxy resin, tetraphenylethane type epoxy resin, and phenol benzopyrrolidone type epoxy resin.

[0027] Specific examples of solid epoxy resins include "HP4032H" (naphthalene-type epoxy resin) manufactured by DIC Corporation; "HP-4700" and "HP-4710" (naphthalene-type tetrafunctional epoxy resin) manufactured by DIC Corporation; "N-690" (cresol novolac-type epoxy resin) manufactured by DIC Corporation; "N-695" (cresol novolac-type epoxy resin) manufactured by DIC Corporation; "HP-7200", "HP-7200HH", "HP-7200H", and "HP-7200L" (dicyclopentadiene-type epoxy resin) manufactured by DIC Corporation; and "HP-7200HH" and "HP-7200H" and "HP-7200L" (dicyclopentadiene-type epoxy resin) manufactured by DIC Corporation. "EXA-7311", "EXA-7311-G3", "EXA-7311-G4", "EXA-7311-G4S", "HP6000", "HP6000L" (naphthyl ether type epoxy resin); "EPPN-502H" (trisphenol type epoxy resin) manufactured by Nippon Kayaku Co., Ltd.; "NC7000L" (naphthol novolac type epoxy resin) manufactured by Nippon Kayaku Co., Ltd.; "NC3000H", "NC3000", "NC3000L", "NC3100FH", "NC3100" (biphenyl type epoxy resin) manufactured by Nippon Kayaku Co., Ltd. Resin); "ESN475V", "ESN4100V" (naphthalene type epoxy resin) manufactured by Nippon Steel Chemicals; "ESN485" (naphthol type epoxy resin) manufactured by Nippon Steel Chemicals; "ESN375" (dihydroxynaphthalene type epoxy resin) manufactured by Nippon Steel Chemicals; "YX4000H", "YX4000", "YX4000HK", "YL7890" (biphenyl type epoxy resin) manufactured by Mitsubishi Chemical; "YL6121" (biphenyl type epoxy resin) manufactured by Mitsubishi Chemical; "YX8800" (anthracene type epoxy resin) manufactured by Mitsubishi Chemical Resin); "YX7700" (phenol aralkyl type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "PG-100" and "CG-500" manufactured by Osaka Gas Chemical Co., Ltd.; "YX7760" (bisphenol AF type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "YL7800" (fluorene type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "jER1010" (bisphenol A type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "jER1031S" (tetraphenylethane type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "WHR991S" (phenol benzopyrrolone type epoxy resin) manufactured by Nippon Kayaku Co., Ltd., etc. These can be used alone or in combination of two or more.

[0028] When a solid epoxy resin and a liquid epoxy resin are used in combination as the epoxy resin (A), their mass ratio (solid epoxy resin:liquid epoxy resin) is preferably 50:1 to 1:10, more preferably 10:1 to 1:2, and particularly preferably 2:1 to 1:1.

[0029] The epoxy equivalent of the (A) epoxy resin is preferably 50 g / eq. to 5,000 g / eq., more preferably 60 g / eq. to 2,000 g / eq., further preferably 70 g / eq. to 1,000 g / eq., and further more preferably 80 g / eq. to 500 g / eq. The epoxy equivalent is the mass of the resin per 1 equivalent of epoxy group. The epoxy equivalent can be measured according to JIS K7236.

[0030] The weight average molecular weight (Mw) of the (A) epoxy resin is preferably 100 to 5,000, more preferably 250 to 3,000, and even more preferably 400 to 1,500. The weight average molecular weight of the resin can be measured as a value in terms of polystyrene by gel permeation chromatography (GPC).

[0031] The content of the epoxy resin (A) in the resin composition is not particularly limited. When the total amount of components other than the organic solvent (B) in the resin composition (non-volatile components) is set to 100% by mass, it is preferably 50% by mass or less, more preferably 40% by mass or less, further preferably 30% by mass or less, further more preferably 25% by mass or less, and particularly preferably 20% by mass or less. The lower limit is preferably 0.5% by mass or more, more preferably 1% by mass or more, further preferably 5% by mass or more, further more preferably 10% by mass or more, and particularly preferably 15% by mass or more.

[0032] <(B) Organic Solvent> The resin composition of the present invention contains (B) an organic solvent. The (B) organic solvent described here is composed of skeleton atoms selected from carbon atoms and oxygen atoms and hydrogen atoms as non-skeleton atoms, and may further have an amide bond (>N-CO-), a urea bond (>N-CO-N<) or a cyano group (-CN) in the molecule in addition to the above-mentioned skeleton atoms, and does not contain a carbon-carbon triple bond or a carbon-carbon double bond (except for the bonds constituting an aromatic ring), and is a liquid compound (liquid compound at normal temperature (25°C)) with a boiling point of 250°C or less (preferably 220°C or less). In addition, the (B) organic solvent described here does not contain substances belonging to (A) epoxy resin or (D) curing agent. It should be noted that in this specification, the boiling point refers to the boiling point (i.e., the standard boiling point) under normal pressure (1atm; 760mmHg). The (B) organic solvent can be used alone or in combination of two or more.

[0033] (B) As the organic solvent, there are mentioned aromatic solvents and non-aromatic solvents.

[0034] Aromatic solvents are solvents containing aromatic rings in the molecule. Examples of aromatic solvents include benzene (boiling point 80°C), toluene (boiling point 110°C), o-xylene (boiling point 144°C), m-xylene (boiling point 139°C), p-xylene (boiling point 138°C), ethylbenzene (boiling point 136°C), etc. 6-8 Aromatic hydrocarbons, 1,2,3-trimethylbenzene (boiling point 176°C), 1,3,5-trimethylbenzene (boiling point 165°C), 1,2,4-trimethylbenzene (boiling point 169°C), 4-ethyltoluene (boiling point 161°C), 3-ethyltoluene (boiling point 160°C), 2-ethyltoluene (boiling point 166°C), isopropylbenzene (boiling point 152°C), n-propylbenzene (boiling point 159°C), indane (boiling point 176°C) and other C9 aromatic hydrocarbons, n-butylbenzene (boiling point 183°C), isobutylbenzene (boiling point 172°C), sec-butylbenzene (boiling point 173°C), tert-butylbenzene (boiling point 169°C), 1,2-diethylbenzene (boiling point 184°C), 1,3-diethylbenzene (boiling point 181°C), 1,4-diethylbenzene (boiling point 183°C), 3-ethyl o-xylene (boiling point 194°C), 4-ethyl o-xylene (boiling point 190°C), 2-ethyl p-xylene (boiling point 187°C), 1-methyl-2-isopropylbenzene (boiling point 178°C), 1-methyl-3-isopropylbenzene (boiling point 175°C), 1-methyl-4-isopropylbenzene (boiling point 177°C), 1,2,3,5-tetramethylbenzene (boiling point 198°C), 1,2,3,4-tetrahydronaphthalene (boiling point 207°C), etc. 10 Aromatic hydrocarbons, 1,3-dimethyl-4-isopropylbenzene (boiling point 199°C), 1-ethyl-4-isopropylbenzene (boiling point 197°C), etc. 11 Aromatic hydrocarbons, 1,4-diisopropylbenzene (boiling point 210°C) and other C 12 Aromatic hydrocarbon solvents such as aromatic hydrocarbons; aromatic ketone solvents such as acetophenone (boiling point 202°C); aromatic alcohol solvents such as benzyl alcohol (boiling point 205°C) and phenylethyl alcohol (boiling point 219-221°C); aromatic ether solvents such as anisole (boiling point 154°C) and phenethyl ether (boiling point 169°C); aromatic ester solvents such as methyl benzoate (boiling point 198-200°C) and ethyl benzoate (boiling point 211-213°C).

[0035] As the aromatic solvent, it is preferred to include an aromatic hydrocarbon solvent. In one embodiment, the aromatic solvent more preferably includes C 6-8 Aromatic hydrocarbons, particularly preferably toluene. In one embodiment, the aromatic solvent more preferably comprises a C9 aromatic hydrocarbon and a C 10 Aromatic solvents among aromatic hydrocarbons.

[0036] As the aromatic solvent, a commercially available aromatic mixed solvent can be used. Examples of commercially available aromatic mixed solvents include: "Ipzole 100" (initial boiling point (initial distillation point) 159°C, dry point 172°C, aromatics 99% or more), "Ipzole 150" (initial boiling point 184°C, dry point 205°C, aromatics 99% or more) manufactured by Idemitsu Kosan Co., Ltd., "Swasol 1000" (initial boiling point 163°C, dry point 175°C, aromatics 100%), "Swasol 150" (initial boiling point 184°C, dry point 205°C, aromatics 99% or more) manufactured by Maruzen Petrochemical Co., Ltd. "Solvent #1500" (initial boiling point 182°C, dry point 206°C, aromatics 98%), "Solvent #100" (initial boiling point 150°C, dry point 185°C), "Solvent #150" (initial boiling point 180°C, dry point 215°C) manufactured by Sankyo Chemical Co., Ltd., etc.

[0037] The non-aromatic solvent is a solvent that does not contain an aromatic ring in the molecule. Examples of the non-aromatic solvent include glycol solvents, glycol ether solvents, glycol ether ester solvents, aliphatic hydrocarbon solvents, aliphatic ketone solvents, aliphatic ester solvents, aliphatic ether solvents, aliphatic alcohol solvents, nitrile solvents, amide solvents, and urea solvents.

[0038] Examples of the glycol solvent include ethylene glycol (boiling point 197° C.), diethylene glycol (boiling point 244° C.), propylene glycol (boiling point 188° C.), dipropylene glycol (boiling point 232° C.), trimethylene glycol (boiling point 211-217° C.), and the like.

[0039] Examples of glycol ether solvents include cellosolves such as ethylene glycol monomethyl ether (also known as methyl cellosolve) (boiling point 124° C.), ethylene glycol monoethyl ether (also known as cellosolve) (boiling point 135° C.), ethylene glycol monopropyl ether (also known as propyl cellosolve) (boiling point 151° C.), ethylene glycol monobutyl ether (also known as butyl cellosolve) (boiling point 171° C.), ethylene glycol monoisobutyl ether (also known as isobutyl cellosolve) (boiling point 160° C.), ethylene glycol monotert-butyl ether (also known as tert-butyl cellosolve) (boiling point 152° C.), and ethylene glycol monohexyl ether (boiling point 208° C.); and cellosolves such as diethylene glycol monomethyl ether (also known as methyl carbitol) (boiling point 193° C.), diethylene glycol monoethyl ether (also known as carbitol) (boiling point 194° C.). Carbitols such as diethylene glycol monobutyl ether (DB) (also known as butyl carbitol) (boiling point 230°C); propylene glycol monomethyl ether (PGM) (boiling point 120°C), propylene glycol monoethyl ether (boiling point 132°C), propylene glycol monopropyl ether (boiling point 150°C), propylene glycol monobutyl ether (boiling point 170°C); dipropylene glycol ethers such as dipropylene glycol monomethyl ether (boiling point 188°C), dipropylene glycol monoethyl ether (boiling point 198°C), dipropylene glycol monopropyl ether (boiling point 210°C), dipropylene glycol monobutyl ether (boiling point 215°C).

[0040] Examples of the glycol ether ester solvent include cellosolve esters such as ethylene glycol monomethyl ether acetate (also known as methyl cellosolve acetate) (boiling point 145° C.), ethylene glycol monoethyl ether acetate (also known as cellosolve acetate) (boiling point 156° C.), and ethylene glycol monobutyl ether acetate (also known as butyl cellosolve acetate) (boiling point 191° C.); carbitol esters such as diethylene glycol monoethyl ether acetate (EDGAc) (also known as carbitol acetate) (boiling point 217° C.), and diethylene glycol monobutyl ether acetate (also known as butyl carbitol acetate) (boiling point 247° C.); propylene glycol ether esters such as propylene glycol monomethyl ether acetate (PGMEA) (boiling point 146° C.), and propylene glycol monoethyl ether acetate (boiling point 160° C.); and dipropylene glycol ether esters such as dipropylene glycol monomethyl ether acetate (boiling point 200° C.).

[0041] Examples of aliphatic hydrocarbon solvents include n-pentane (boiling point 36°C), n-hexane (boiling point 69°C), 2-methylpentane (also known as isohexane) (boiling point 60-62°C), n-heptane (boiling point 98°C), n-octane (boiling point 125°C), cyclopentane (boiling point 49°C), cyclohexane (boiling point 81°C), methylcyclohexane (boiling point 101°C), and ethylcyclohexane (boiling point 132°C).

[0042] Examples of the aliphatic ketone solvent include aliphatic non-cyclic ketones such as acetone (boiling point 56°C), methyl ethyl ketone (MEK) (boiling point 79°C), diethyl ketone (boiling point 101°C), 2-pentanone (boiling point 101°C), methyl isobutyl ketone (boiling point 116°C), 2-hexanone (boiling point 127°C), 2-heptanone (MAK) (boiling point 151°C), and diisobutyl ketone (boiling point 168°C); and aliphatic cyclic ketones such as cyclopentanone (boiling point 131°C), cyclohexanone (Anone) (boiling point 155°C), and 2-methylcyclohexanone (boiling point 162°C).

[0043] The aliphatic ester solvent is a non-aromatic solvent having an ester structure that does not belong to the glycol ether ester solvent, and examples thereof include methyl acetate (boiling point 57° C.), ethyl acetate (boiling point 77° C.), n-propyl acetate (boiling point 96° C.), isopropyl acetate (boiling point 89° C.), n-butyl acetate (boiling point 126° C.), isobutyl acetate (boiling point 118° C.), sec-butyl acetate (boiling point 112° C.), tert-butyl acetate (boiling point 97° C.), n-amyl acetate (boiling point 149° C.), isoamyl acetate (boiling point 142° C.), and tert-butyl acetate (boiling point 97° C.). ℃), ethyl propionate (boiling point 99℃), propyl propionate (boiling point 122℃), isopropyl propionate (boiling point 108℃), etc. fatty acid alkyl esters; methyl lactate (boiling point 144-145℃), ethyl lactate (boiling point 151-155℃), butyl lactate (boiling point 185-187℃), etc. hydroxy acid alkyl esters; methyl acetoacetate (boiling point 170℃), ethyl acetoacetate (boiling point 184℃), etc. keto acid alkyl esters; γ-butyrolactone (GBL) (boiling point 204℃) and other lactones.

[0044] Aliphatic ether solvents are non-aromatic solvents with an ether structure that do not belong to glycol ether solvents and glycol ether ester solvents, and include, for example, aliphatic non-cyclic ethers such as diethyl ether (boiling point 34°C), diisopropyl ether (boiling point 68°C), and methyl tert-butyl ether (boiling point 55°C); and aliphatic cyclic ethers such as tetrahydrofuran (boiling point 66°C), 1,4-dioxane (boiling point 101°C), and 1,3-dioxolane (boiling point 75°C).

[0045] Aliphatic alcohol solvents are non-aromatic solvents having an alcohol structure that do not belong to glycol solvents and glycol ether solvents, and examples thereof include methanol (boiling point 64°C), ethanol (boiling point 78°C), n-propanol (boiling point 97°C), isopropanol (boiling point 82°C), n-butanol (boiling point 117°C), isobutanol (boiling point 108°C), sec-butanol (boiling point 99°C), tert-butanol (boiling point 82°C), n-pentanol (boiling point 138°C), and tert-butanol (boiling point 82°C). ), isopentanol (boiling point 131°C), sec-pentanol (boiling point 119°C), tert-pentanol (boiling point 102°C), neopentyl alcohol (boiling point 113°C), n-hexanol (boiling point 157°C), n-heptanol (boiling point 175°C), isoheptanol (boiling point 159°C), n-octanol (boiling point 195°C), 2-ethylhexanol (boiling point 184°C), etc.; aliphatic cyclic alcohols such as cyclohexanol (boiling point 161°C).

[0046] Examples of the nitrile solvent include acetonitrile (boiling point: 82° C.) and propionitrile (boiling point: 97° C.).

[0047] Examples of the amide solvent include non-cyclic amides such as N,N-dimethylformamide (DMF) (boiling point 153° C.) and N,N-dimethylacetamide (DMA) (boiling point 165° C.); and cyclic amides such as N-methyl-2-pyrrolidone (NMP) (boiling point 202° C.).

[0048] Examples of the urea solvent include acyclic ureas such as tetramethylurea (boiling point 176° C.); and cyclic ureas such as 1,3-dimethyl-2-imidazolidinone (DMI) (boiling point 220° C.) and N,N′-dimethylpropyleneurea (DMPU) (boiling point 246° C.).

[0049] As the non-aromatic solvent, it is preferable to include a non-aromatic solvent selected from glycol ether-based solvents and aliphatic ketone-based solvents.

[0050] The content of the organic solvent having a boiling point of less than 100° C. in the organic solvent (B), when the total amount of the organic solvent (B) contained in the resin composition is set to 100 mass%, has a lower limit of 5 mass% or more, preferably 8 mass% or more, more preferably 10 mass% or more, particularly preferably 12 mass% or more, and an upper limit of 60 mass% or less, preferably 58 mass% or less, and more preferably 56 mass% or less.

[0051] The content of the organic solvent having a boiling point of 130° C. or higher in the organic solvent (B), when the total amount of the organic solvent (B) contained in the resin composition is 100% by mass, is preferably 1% by mass or higher, more preferably 5% by mass or higher, further preferably 10% by mass or higher, further more preferably 15% by mass or higher, further preferably 20% by mass or higher, particularly preferably 25% by mass or higher, and the upper limit is 95% by mass or lower, preferably 90% by mass or lower, more preferably 85% by mass or lower, particularly preferably 80% by mass or lower.

[0052] The content of the organic solvent having a boiling point of 100° C. or higher and less than 130° C. in the organic solvent (B), when the total amount of the organic solvent (B) contained in the resin composition is 100 mass %, has a lower limit of 0 mass % or higher, preferably 0.1 mass % or higher, more preferably 0.5 mass % or higher, further preferably 1 mass % or higher, further more preferably 3 mass % or higher, particularly preferably 5 mass % or higher, and an upper limit of 95 mass % or lower, preferably 70 mass % or lower, more preferably 50 mass % or lower, further preferably 40 mass % or lower, further more preferably 30 mass % or lower, further more preferably 25 mass % or lower, and particularly preferably 20 mass % or lower.

[0053] The content of the organic solvent having a boiling point of less than 75° C. in the organic solvent (B), when the total amount of the organic solvent (B) contained in the resin composition is 100% by mass, has a lower limit of 0% by mass and an upper limit of preferably 50% by mass or less, more preferably 30% by mass or less, further preferably 10% by mass or less, further more preferably 5% by mass or less, further preferably 1% by mass or less, and particularly preferably 0.1% by mass or less.

[0054] The content of the organic solvent having a boiling point of 220° C. or higher in the organic solvent (B), when the total amount of the organic solvent (B) contained in the resin composition is set to 100% by mass, has a lower limit of 0% by mass and an upper limit of preferably 10% by mass or lower, more preferably 5% by mass or lower, further preferably 1% by mass or lower, and particularly preferably 0.1% by mass or lower.

[0055] The content of the non-aromatic solvent in the (B) organic solvent, when the total amount of the (B) organic solvent contained in the resin composition is 100 mass %, has a lower limit of, for example, 0 mass %, preferably 1 mass % or more, more preferably 5 mass % or more, further preferably 10 mass % or more, particularly preferably 15 mass % or more, and an upper limit of 65 mass % or less.

[0056] The content of the non-aromatic solvent having a boiling point of 130° C. or higher in the (B) organic solvent, when the total amount of the (B) organic solvent contained in the resin composition is 100 mass %, has a lower limit of, for example, 0 mass % or higher, preferably 0.1 mass % or higher, more preferably 1 mass % or higher, further preferably 1.5 mass % or higher, particularly preferably 2 mass % or higher, and most preferably 2.5 mass % or higher, and an upper limit of 60 mass % or lower, preferably 50 mass % or lower, more preferably 40 mass % or lower, further preferably 30 mass % or lower, further more preferably 20 mass % or lower, and particularly preferably 10 mass % or lower.

[0057] The content of the aromatic solvent in the (B) organic solvent, when the total amount of the (B) organic solvent contained in the resin composition is 100 mass %, has a lower limit of 35 mass % or more and an upper limit of, for example, 100 mass % or less, preferably 99 mass % or less, more preferably 95 mass % or less, further preferably 90 mass % or less, particularly preferably 85 mass % or less, and most preferably 80 mass % or less.

[0058] The content of the aromatic solvent having a boiling point of 130° C. or higher (preferably 160° C. or higher) in the (B) organic solvent, when the total amount of the (B) organic solvent contained in the resin composition is 100% by mass, has a lower limit of, for example, 0% by mass or higher, preferably 1% by mass or higher, more preferably 5% by mass or higher, further preferably 10% by mass or higher, further more preferably 15% by mass or higher, particularly preferably 20% by mass or higher, and an upper limit of 95% by mass or lower, preferably 90% by mass or lower, more preferably 87% by mass or lower, further preferably 85% by mass or lower, particularly preferably 83% by mass or lower, and most preferably 80% by mass or lower.

[0059] The content of the aromatic solvent having a boiling point of 130° C. or higher (preferably 160° C. or higher) in the aromatic solvent, when the total amount of the aromatic solvent contained in the resin composition is set to 100% by mass, is, for example, 0% by mass or higher in the lower limit, preferably 1% by mass or higher, more preferably 10% by mass or higher, further preferably 20% by mass or higher, further more preferably 30% by mass or higher, further preferably 40% by mass or higher, particularly preferably 50% by mass or higher, particularly preferably 60% by mass or higher, and the upper limit is 100% by mass or lower.

[0060] The content of the organic solvent selected from the group consisting of aromatic hydrocarbon solvents and aliphatic ketone solvents in the (B) organic solvent is preferably 50% by mass or more, more preferably 70% by mass or more, further preferably 80% by mass or more, further more preferably 90% by mass or more, and particularly preferably 95% by mass or more, when the total amount of the (B) organic solvent contained in the resin composition is set to 100% by mass.

[0061] The content of the organic solvent (B) formed of constituent atoms selected from carbon atoms, oxygen atoms and hydrogen atoms (organic solvent not containing nitrogen atoms) in the organic solvent is preferably 60 mass% or more, more preferably 80 mass% or more, further preferably 90 mass% or more, further more preferably 95 mass% or more, further more preferably 98 mass% or more, and particularly preferably 99 mass% or more, when the total amount of the organic solvent (B) contained in the resin composition is 100 mass%.

[0062] The content of the (B) organic solvent in the resin composition, when all the components in the resin composition are set to 100% by mass, is preferably 1% by mass or more in the lower limit, more preferably 5% by mass or more, further preferably 10% by mass or more, further more preferably 13% by mass or more, further more preferably 15% by mass or more, and particularly preferably 17% by mass or more in the upper limit, and is preferably 90% by mass or less, more preferably 70% by mass or less, further preferably 60% by mass or less, further more preferably 55% by mass or less, and particularly preferably 50% by mass or less in the upper limit.

[0063] <(C) Inorganic filler> The resin composition of the present invention contains (C) an inorganic filler. The (C) inorganic filler is contained in the resin composition in the form of particles.

[0064] Inorganic compounds are used as materials of (C) inorganic fillers. As materials of (C) inorganic fillers, for example, silica, aluminum oxide, glass, cordierite, silicon oxide, barium sulfate, barium carbonate, talc, clay, mica powder, zinc oxide, hydrotalcite, boehmite, aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, magnesium oxide, boron nitride, aluminum nitride, manganese nitride, aluminum borate, strontium carbonate, strontium titanate, calcium titanate, magnesium titanate, bismuth titanate, titanium oxide, zirconium oxide, barium titanate, barium zirconate, calcium zirconate, zirconium phosphate and zirconium tungstate phosphate, etc., can be cited. Among them, silica is particularly preferred. As silica, for example, amorphous silica, fused silica, crystalline silica, synthetic silica, hollow silica, etc. can be cited. In addition, as silica, spherical silica is preferred. (C) Inorganic fillers can be used alone or in combination of two or more in any ratio.

[0065] (C) Commercially available products of the inorganic filler include, for example, "SP60-05" and "SP507-05" manufactured by Nippon Steel Chemicals Co., Ltd.; "YC100C", "YA050C", "YA050C-MJE", "YA010C", "SC2500SQ", "SO-C4", "SO-C2", and "SO-C1" manufactured by Yaduma Co., Ltd.; "UFP-30", "DAW-03", and "FB-105FD" manufactured by Denka Co., Ltd.; "Silfil NSS-3N", "Silfil NSS-4N", and "Silfil NSS-5N" manufactured by Tokuyama Co., Ltd.; "CellSpheres" and "MGH-005" manufactured by Pacific Cement Co., Ltd.; and "Exfil" and "BA-1" manufactured by JGC Catalysts & Chemicals Co., Ltd.

[0066] (C) The average particle size of the inorganic filler is not particularly limited, preferably 10 μm or less, more preferably 5 μm or less, further preferably 3 μm or less, further preferably 2 μm or less, and particularly preferably 1 μm or less. (C) The lower limit of the average particle size of the inorganic filler is not particularly limited, preferably 0.01 μm or more, more preferably 0.05 μm or more, further preferably 0.1 μm or more, and particularly preferably 0.2 μm or more. (C) The average particle size of the inorganic filler can be measured by a laser diffraction / scattering method based on Mie scattering theory. Specifically, a particle size distribution of an inorganic filler can be prepared on a volume basis by a laser diffraction scattering particle size distribution measuring device, and the median particle size can be measured as the average particle size. The sample can be measured using a sample obtained by weighing 100 mg of an inorganic filler and 10 g of methyl ethyl ketone in a vial and dispersing it with ultrasound for 10 minutes. For the measurement sample, a laser diffraction particle size distribution measuring device is used, the wavelength of the light source is set to blue and red, and the volume-based particle size distribution of the inorganic filler is measured by a flow cell method, and the average particle size is calculated as the median particle size based on the obtained particle size distribution. As a laser diffraction particle size distribution measuring device, for example, "LA-960" made by Horiba Manufacturing Co., Ltd. can be cited.

[0067] (C) The specific surface area of ​​the inorganic filler is not particularly limited, but is preferably 0.1 m 2 / g or more, more preferably 0.5m 2 / g or more, more preferably 1m 2 / g or more, particularly preferably 3m 2 The upper limit of the specific surface area of ​​the inorganic filler (C) is not particularly limited, but is preferably 100 m 2 / g or less, more preferably 70m 2 / g or less, more preferably 50m2 / g or less, and more preferably 30m 2 / g or less, particularly preferably 10m 2 The specific surface area of ​​the inorganic filler is calculated by adsorbing nitrogen on the surface of a sample using a specific surface area measuring apparatus (Macsorb HM-1210 manufactured by Mountech) according to the BET method and using the BET multipoint method.

[0068] From the viewpoint of improving moisture resistance and dispersibility, (C) inorganic filler is preferably treated with a surface treatment agent. As the surface treatment agent, for example, fluorine-containing silane coupling agents, aminosilane coupling agents, epoxysilane coupling agents, mercaptosilane coupling agents, silane coupling agents, alkoxysilanes, organosilazane compounds, titanate coupling agents, etc. can be cited. In addition, the surface treatment agent can be used alone or in any combination of two or more.

[0069] Commercially available products of the surface treatment agent include, for example, “KBM403” (3-glycidoxypropyltrimethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd., “KBM803” (3-mercaptopropyltrimethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd., “KBE903” (3-aminopropyltriethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd., “KBM573” (N-phenyl-3-aminopropyltrimethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd., “SZ-31” (hexamethyldisilazane) manufactured by Shin-Etsu Chemical Co., Ltd., “KBM103” (phenyltrimethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd., “KBM-4803” (long-chain epoxy-type silane coupling agent) manufactured by Shin-Etsu Chemical Co., Ltd., and “KBM-7103” (3,3,3-trifluoropropyltrimethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd.

[0070] From the viewpoint of improving the dispersibility of the inorganic filler, the degree of surface treatment performed by the surface treatment agent is preferably within a specified range. Specifically, 100% by mass of the inorganic filler is preferably surface treated with 0.2% by mass to 5% by mass of the surface treatment agent, more preferably with 0.2% by mass to 3% by mass, and further preferably with 0.3% by mass to 2% by mass.

[0071] The degree of surface treatment by the surface treatment agent can be evaluated by the carbon content per unit surface area of ​​the inorganic filler. From the viewpoint of improving the dispersibility of the inorganic filler, the carbon content per unit surface area of ​​the inorganic filler is preferably 0.02 mg / m 2 More preferably 0.1 mg / m 2 More preferably, 0.2 mg / m 2On the other hand, from the viewpoint of preventing the melt viscosity of the resin composition from increasing, it is preferably 1.0 mg / m 2 Below, more preferably 0.8 mg / m 2 Below, more preferably 0.5 mg / m 2 the following.

[0072] (C) The amount of carbon per unit surface area of ​​the inorganic filler can be measured after the surface-treated inorganic filler is cleaned with a solvent (e.g., methyl ethyl ketone (MEK)). Specifically, a sufficient amount of MEK is added as a solvent to the inorganic filler surface-treated with a surface treatment agent, and ultrasonic cleaning is performed at 25°C for 5 minutes. After removing the supernatant and drying the solid component, the amount of carbon per unit surface area of ​​the inorganic filler can be measured using a carbon analyzer. As a carbon analyzer, "EMIA-320V" manufactured by Horiba, Ltd. can be used.

[0073] The content of the (C) inorganic filler in the resin composition, when the total amount of the components other than the (B) organic solvent in the resin composition (non-volatile components) is set to 100 mass%, the upper limit is preferably 90 mass% or less, more preferably 85 mass% or less, further preferably 80 mass% or less, and particularly preferably 78 mass% or less, and the lower limit is preferably 1 mass% or more, preferably 10 mass% or more, more preferably 30 mass% or more, further preferably 40 mass% or more, further more preferably 50 mass% or more, further preferably 60 mass% or more, and particularly preferably 70 mass% or more.

[0074] The mass ratio of the (C) inorganic filler to the (A) epoxy resin in the resin composition ((C) inorganic filler / (A) epoxy resin) is not particularly limited, but is preferably 1 or more, more preferably 2 or more, and particularly preferably 4 or more. The upper limit is not particularly limited, but is preferably 20 or less, more preferably 10 or less, and particularly preferably 5 or less.

[0075] The total content of the (A) epoxy resin and the (C) inorganic filler in the resin composition is preferably 70% by mass or more, more preferably 80% by mass or more, further preferably 85% by mass or more, and particularly preferably 90% by mass or more, when the total amount of the components other than the (B) organic solvent in the resin composition (non-volatile components) is set to 100% by mass.

[0076] <(D) Curing agent> The resin composition of the present invention may contain (D) a curing agent as an optional component (optionally contained component). The (D) curing agent may be used alone or in any combination of two or more. The (D) curing agent may have a function of reacting with the (A) epoxy resin to cure it.

[0077] The (D) curing agent is not particularly limited, and examples thereof include active ester curing agents, phenolic curing agents, carbodiimide curing agents, anhydride curing agents, amine curing agents, benzoxazine curing agents, cyanate curing agents, and thiol curing agents. In one embodiment, from the viewpoint of suppressing the dielectric loss tangent to a lower level, the (D) curing agent particularly preferably includes an active ester curing agent. In addition, in one embodiment, from the viewpoint of further improving the curability, the (D) curing agent particularly preferably includes a phenolic curing agent.

[0078] As active ester curing agent, generally preferably use phenolic esters, thiophenolic esters, N-hydroxylamine esters, esters of heterocyclic hydroxy compounds, etc., which have ester groups with more than 2 high reactive activities in 1 molecule. The active ester compound is preferably obtained by the condensation reaction of carboxylic acid compounds and / or thiocarboxylic acid compounds with hydroxy compounds and / or thiol compounds. Particularly from the viewpoint of improving heat resistance, preferably the active ester compound obtained by carboxylic acid compounds and hydroxy compounds, more preferably the active ester compound obtained by carboxylic acid compounds and phenolic compounds and / or naphthol compounds. As carboxylic acid compounds, for example benzoic acid, acetic acid, succinic acid, maleic acid, itaconic acid, phthalic acid, isophthalic acid, terephthalic acid, pyromellitic acid, etc. can be mentioned. Examples of the phenol compound or naphthol compound include hydroquinone, resorcinol, bisphenol A, bisphenol F, bisphenol S, phenolphthalein, methylated bisphenol A, methylated bisphenol F, methylated bisphenol S, phenol, o-cresol, m-cresol, p-cresol, catechol, α-naphthol, β-naphthol, 1,5-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 2,6-dihydroxynaphthalene, dihydroxybenzophenone, trihydroxybenzophenone, tetrahydroxybenzophenone, phloroglucinol, pyrogallol, dicyclopentadiene-type diphenol compounds, and phenolic novolac. Here, the so-called "dicyclopentadiene-type diphenol compound" refers to a diphenol compound obtained by condensing two molecules of phenol with one molecule of dicyclopentadiene.

[0079] Specifically, the active ester curing agent is preferably a dicyclopentadiene type active ester compound, a naphthalene type active ester compound containing a naphthalene structure, an active ester compound containing an acetylated product of a novolac resin, and an active ester compound containing a benzoylated product of a novolac resin, and more preferably at least one selected from the group consisting of a dicyclopentadiene type active ester compound and a naphthalene type active ester compound. As the dicyclopentadiene type active ester compound, an active ester compound containing a dicyclopentadiene type diphenol structure is preferred.

[0080] As for commercially available products of active ester curing agents, as active ester compounds containing a dicyclopentadiene-type diphenol structure, there are "EXB 9451", "EXB 9460", "EXB 9460S", "HPC-8000L-65TM", "HPC-8000-65T", "HPC-8000H", "HPC-8000H-65TM" (manufactured by DIC Corporation); as active ester compounds containing a naphthalene structure, there are "HP-B-8151-62T", "EXB-8100L-65T", "EXB-9416-70BK", "HPC-8150-62T", "EXB-8" (manufactured by DIC Corporation); as active ester compounds containing phosphorus, there are "EXB 9401" (manufactured by DIC Corporation); as an active ester compound containing an acetylated product of a linear phenolic resin, "DC808" (manufactured by Mitsubishi Chemical Corporation) can be cited; as an active ester compound containing a benzoylated product of a linear phenolic resin, "YLH1026", "YLH1030" and "YLH1048" (manufactured by Mitsubishi Chemical Corporation) can be cited; as an active ester compound containing a styryl group and a naphthalene structure, "PC1300-02-65MA" (manufactured by Air Water Corporation) and the like can be cited.

[0081] As the phenolic curing agent, from the viewpoint of heat resistance and water resistance, a phenolic curing agent having a phenolic structure is preferred. In addition, from the viewpoint of adhesion to the adherend, a nitrogen-containing phenolic curing agent is preferred, and a phenolic curing agent containing a triazine skeleton is more preferred. Among them, from the viewpoint of highly satisfying heat resistance, water resistance and adhesion, a linear phenolic resin containing a triazine skeleton is preferred. Specific examples of phenolic curing agents include "MEH-7700", "MEH-7810", and "MEH-7851" manufactured by Meiwa Chemicals, "NHN", "CBN", and "GPH" manufactured by Nippon Kayaku Co., Ltd., "SN-170", "SN-180", "SN-190", "SN-475", "SN-485", "SN-495", "SN-375", and "SN-395" manufactured by Nippon Steel Chemicals Co., Ltd., and "LA-7052", "LA-7054", "LA-3018", "LA-3018-50P", "LA-1356", "TD 2090", and "KA-1160" manufactured by DIC Corporation.

[0082] Examples of the carbodiimide curing agent include curing agents having one or more, preferably two or more, carbodiimide structures in one molecule, for example, aliphatic biscarbodiimides such as tetramethylene-bis(tert-butylcarbodiimide) and cyclohexanebis(methylene-tert-butylcarbodiimide); aromatic biscarbodiimides such as phenylene-bis(xylylcarbodiimide); aliphatic polycarbodiimides such as polyhexamethylenecarbodiimide, polytrimethylhexamethylenecarbodiimide, polycyclohexylcarbodiimide, poly(methylenebiscyclohexylcarbodiimide), poly(isophoronecarbodiimide); Imides; aromatic polycarbodiimides such as poly(phenylene carbodiimide), poly(naphthylene carbodiimide), poly(tolylene carbodiimide), poly(methyl diisopropyl phenylene carbodiimide), poly(triethyl phenylene carbodiimide), poly(diethyl phenylene carbodiimide), poly(triisopropyl phenylene carbodiimide), poly(diisopropyl phenylene carbodiimide), poly(xylylene carbodiimide), poly(tetramethyl xylylene carbodiimide), poly(methylene diphenylene carbodiimide), poly[methylene bis(methyl phenylene) carbodiimide], etc.

[0083] Examples of commercially available carbodiimide curing agents include "CARBODILITE V-02B", "CARBODILITE V-03", "CARBODILITE V-04K", "CARBODILITE V-07" and "CARBODILITE V-09" manufactured by Nisshinbo Chemical Co., Ltd.; and "Stabaxol P", "Stabaxol P400" and "Hycasyl 510" manufactured by Rhein-Chemie.

[0084] As the acid anhydride curing agent, there can be mentioned a curing agent having one or more acid anhydride groups in one molecule, preferably a curing agent having two or more acid anhydride groups in one molecule. Specific examples of the acid anhydride curing agent include phthalic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, methylnadic anhydride, hydrogenated methylnadic anhydride, trialkyltetrahydrophthalic anhydride, dodecenylsuccinic anhydride, 5-(2,5-dioxotetrahydro-3-furanyl)-3-methyl-3-cyclohexene-1,2-dicarboxylic anhydride, trimellitic anhydride, pyromellitic anhydride , dibenzophenone tetracarboxylic dianhydride, biphenyl tetracarboxylic dianhydride, naphthalene tetracarboxylic dianhydride, oxydiphthalic dianhydride, 3,3'-4,4'-diphenylsulfone tetracarboxylic dianhydride, 1,3,3a,4,5,9b-hexahydro-5-(tetrahydro-2,5-dioxo-3-furanyl)-naphtho[1,2-C]furan-1,3-dione, ethylene glycol ditrimellitate, styrene-maleic acid resin obtained by copolymerization of styrene and maleic acid, and other polymer-type acid anhydrides. Commercially available products of anhydride curing agents include "HNA-100", "MH-700", "MTA-15", "DDSA", and "OSA" manufactured by Shin Nippon Rika Co., Ltd., "YH-306" and "YH-307" manufactured by Mitsubishi Chemical Corporation, "HN-2200" and "HN-5500" manufactured by Hitachi Chemical Co., Ltd., and "EF-30", "EF-40", "EF-60", and "EF-80" manufactured by Cray Valley Co., Ltd.

[0085] As the amine curing agent, there can be mentioned a curing agent having one or more, preferably two or more amino groups in one molecule, such as aliphatic amines, polyether amines, alicyclic amines, aromatic amines, etc. Among them, from the viewpoint of exerting the desired effect of the present invention, aromatic amines are preferred. The amine curing agent is preferably a primary amine or a secondary amine, and more preferably a primary amine. As specific examples of the amine curing agent, there can be mentioned 4,4'-methylenebis(2,6-dimethylaniline), 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenyl sulfone, 3,3'-diaminodiphenyl sulfone, metaphenylenediamine, metaxylene diamine, diethyltoluenediamine, 4,4'-diaminodiphenyl ether, 3,3'-dimethyl-4,4'-diaminobiphenyl, 2,2'-dimethyl-4,4'-diaminobiphenyl, 3,3'-dihydroxybenzidine, 2,2-bis(3-amino-4-hydroxy phenyl)propane, 3,3-dimethyl-5,5-diethyl-4,4-diphenylmethanediamine, 2,2-bis(4-aminophenyl)propane, 2,2-bis(4-(4-aminophenoxy)phenyl)propane, 1,3-bis(3-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, 4,4'-bis(4-aminophenoxy)biphenyl, bis(4-(4-aminophenoxy)phenyl)sulfone, bis(4-(3-aminophenoxy)phenyl)sulfone, etc. Amine curing agents that can be used are commercially available products, and examples thereof include "SEIKACURE-S" manufactured by Seika Corporation, "KAYABOND C-200S", "KAYABOND C-100", "KAYAHARD AA", "KAYAHARD AB", and "KAYAHARD AS" manufactured by Nippon Kayaku Co., Ltd., and "Epicure W" manufactured by Mitsubishi Chemical Corporation.

[0086] Specific examples of the benzoxazine-based curing agent include “JBZ-OP100D” and “ODA-BOZ” manufactured by JFE Chemical Co., Ltd.; “HFB2006M” manufactured by Showa High Molecular Co., Ltd.; and “Pd” and “Fa” manufactured by Shikoku Chemical Industry Co., Ltd.

[0087] Examples of the cyanate curing agent include difunctional cyanate resins such as bisphenol A dicyanate, polyphenol cyanate, oligo(3-methylene-1,5-phenylene cyanate), 4,4'-methylenebis(2,6-dimethylphenylcyanate), 4,4'-ethylidene diphenyl dicyanate, hexafluorobisphenol A dicyanate, 2,2-bis(4-cyano)phenylpropane, 1,1-bis(4-cyanophenylmethane), bis(4-cyano-3,5-dimethylphenyl)methane, 1,3-bis(4-cyanophenyl-1-(methylethylidene))benzene, bis(4-cyanophenyl)sulfide and bis(4-cyanophenyl)ether; polyfunctional cyanate resins derived from phenol novolac resins and cresol novolac resins; and prepolymers obtained by triazinization of a portion of these cyanate resins. Specific examples of cyanate curing agents include "PT30" and "PT60" manufactured by Lonza Japan (both are linear phenolic polyfunctional cyanate resins), "BA230", and "BA230S75" (prepolymers in which a part or all of bisphenol A dicyanate is triazine-treated to form a trimer), etc.

[0088] Examples of the thiol-based curing agent include trimethylolpropane tris(3-mercaptopropionate), pentaerythritol tetrakis(3-mercaptobutyrate), and tris(3-mercaptopropyl)isocyanurate.

[0089] The reactive group equivalent of the (D) curing agent is preferably 50 g / eq. to 3000 g / eq., more preferably 100 g / eq. to 1000 g / eq., further preferably 100 g / eq. to 500 g / eq., and particularly preferably 100 g / eq. to 300 g / eq. The reactive group equivalent is the mass of the (D) curing agent per 1 equivalent of reactive groups.

[0090] When a phenolic curing agent is included as the curing agent (D), the content of the phenolic curing agent in the resin composition is preferably 0.5% by mass or more from the viewpoint of further improving the curability, and is preferably 5% by mass or less, and more preferably 3% by mass or less, from the viewpoint of further suppressing the dielectric loss tangent.

[0091] When the (D) curing agent includes an active ester curing agent, the content of the active ester curing agent in the resin composition is preferably 0.1% by mass or more, more preferably 1% by mass or more, further preferably 3% by mass or more, and particularly preferably 5% by mass or more, when the total amount of the components (non-volatile components) other than the (B) organic solvent in the resin composition is set to 100% by mass, from the viewpoint of suppressing the dielectric loss tangent to a lower level. In addition, the content of the active ester curing agent in the resin composition is preferably 10% by mass or more, more preferably 30% by mass or more, further preferably 40% by mass or more, and particularly preferably 50% by mass or more, when the (D) curing agent in the resin composition is set to 100% by mass, from the viewpoint of suppressing the dielectric loss tangent to a lower level.

[0092] The content of the (D) curing agent in the resin composition is not particularly limited. When the total amount of the components other than the (B) organic solvent in the resin composition (non-volatile components) is set to 100 mass%, it is preferably 30 mass% or less, more preferably 20 mass% or less, further preferably 15 mass% or less, and particularly preferably 10 mass% or less. The lower limit may be 0 mass% or more, 0.01 mass% or more, 0.1 mass% or more, and may be preferably 1 mass% or more, more preferably 3 mass% or more, and particularly preferably 5 mass% or more.

[0093] The mass ratio of the (D) curing agent to the (A) epoxy resin in the resin composition ((D) curing agent / (A) epoxy resin) is not particularly limited, but is preferably 0.02 or more, more preferably 0.05 or more, and particularly preferably 0.2 or more. The upper limit is not particularly limited, but is preferably 2 or less, more preferably 1 or less, and particularly preferably 0.5 or less.

[0094] The total content of (A) epoxy resin, (C) inorganic filler and (D) curing agent in the resin composition is preferably 80% by mass or more, more preferably 90% by mass or more, further preferably 95% by mass or more, and particularly preferably 98% by mass or more, when the total amount of components other than (B) organic solvent in the resin composition (non-volatile components) is set to 100% by mass.

[0095] <(E) Thermoplastic resin> The resin composition of the present invention may further contain (E) a thermoplastic resin as an optional component. The (E) thermoplastic resin described here is a component other than the (A) epoxy resin and (D) curing agent described above.

[0096] As (E) thermoplastic resin, for example, polyimide resin, phenoxy resin, polyvinyl acetal resin, polyolefin resin, polybutadiene resin, polyamide-imide resin, polyetherimide resin, polysulfone resin, polyethersulfone resin, polyphenylene ether resin, polycarbonate resin, polyetheretherketone resin, polyester resin, etc. can be cited. In one embodiment, (E) thermoplastic resin preferably includes a thermoplastic resin selected from polyimide resin and phenoxy resin, and more preferably includes phenoxy resin. In addition, the thermoplastic resin can be used alone or in combination of two or more.

[0097] Specific examples of the polyimide resin include "SLK-6100" manufactured by Shin-Etsu Chemical Co., Ltd., and "RIKACOAT SN20" and "RIKACOAT PN20" manufactured by Shin Nippon Chemical Co., Ltd.

[0098] Examples of the phenoxy resin include phenoxy resins having one or more skeletons selected from the group consisting of bisphenol A skeleton, bisphenol F skeleton, bisphenol S skeleton, bisphenol acetophenone skeleton, phenolic skeleton, biphenyl skeleton, fluorene skeleton, dicyclopentadiene skeleton, norbornene skeleton, naphthalene skeleton, anthracene skeleton, adamantane skeleton, terpene skeleton, and trimethylcyclohexane skeleton. The terminal of the phenoxy resin may be any functional group such as a phenolic hydroxyl group or an epoxy group.

[0099] Specific examples of phenoxy resins include "1256" and "4250" manufactured by Mitsubishi Chemical Corporation (both are phenoxy resins containing a bisphenol A skeleton); "YX8100" manufactured by Mitsubishi Chemical Corporation (a phenoxy resin containing a bisphenol S skeleton); "YX6954" manufactured by Mitsubishi Chemical Corporation (a phenoxy resin containing a bisphenol acetophenone skeleton), "FX280" and "FX293" manufactured by Nippon Steel Chemical Materials Co., Ltd.; "YX7200B35", "YL7500BH30", "YX6954BH30", "YX7553BH30", "YL7769BH30", "YL6794", "YL7213", "YL7290" and "YL7482" manufactured by Mitsubishi Chemical Corporation.

[0100] Examples of the polyvinyl acetal resin include polyvinyl formal resin and polyvinyl butyral resin, and polyvinyl butyral resin is preferred. Specific examples of the polyvinyl acetal resin include "Denka Butyral 4000-2", "Denka Butyral 5000-A", "Denka Butyral 6000-C", and "Denka Butyral 6000-EP" manufactured by Denki Kagaku Kogyo Co., Ltd.; and S-LEC BH series, BX series (e.g., BX-5Z), KS series (e.g., KS-1), BL series, and BM series manufactured by Sekisui Chemical Co., Ltd.

[0101] Examples of the polyolefin resin include ethylene copolymer resins such as low-density polyethylene, ultra-low-density polyethylene, high-density polyethylene, ethylene-vinyl acetate copolymers, ethylene-ethyl acrylate copolymers, and ethylene-methyl acrylate copolymers; and polyolefin polymers such as polypropylene and ethylene-propylene block copolymers.

[0102] Examples of the polybutadiene resin include a resin containing a hydrogenated polybutadiene skeleton, a polybutadiene resin containing a hydroxyl group, a polybutadiene resin containing a phenolic hydroxyl group, a polybutadiene resin containing a carboxyl group, a polybutadiene resin containing an acid anhydride group, a polybutadiene resin containing an epoxy group, a polybutadiene resin containing an isocyanate group, a polybutadiene resin containing a urethane group, and a polyphenylene ether-polybutadiene resin.

[0103] Specific examples of the polyamideimide resin include "VYLOMAX HR11NN" and "VYLOMAX HR16NN" manufactured by Toyobo Co., Ltd. Specific examples of the polyamideimide resin include modified polyamideimides such as "KS9100" and "KS9300" (polyamideimide containing a polysiloxane skeleton) manufactured by Hitachi Chemical Co., Ltd.

[0104] Specific examples of the polyethersulfone resin include "PES5003P" manufactured by Sumitomo Chemical Co., Ltd. and the like.

[0105] Specific examples of the polysulfone resin include polysulfone "P1700" and "P3500" manufactured by Solvay Advanced Polymers.

[0106] Specific examples of the polyphenylene ether resin include "NORYL SA90" manufactured by SABIC, etc. Specific examples of the polyetherimide resin include "Ultem" manufactured by GE, etc.

[0107] As polycarbonate resins, there can be mentioned hydroxyl-containing carbonate resins, phenolic hydroxyl-containing carbonate resins, carboxyl-containing carbonate resins, anhydride-containing carbonate resins, isocyanate-containing carbonate resins, urethane-containing carbonate resins, etc. As specific examples of polycarbonate resins, there can be mentioned "FPC0220" manufactured by Mitsubishi Gas Chemical Co., Ltd., "T6002", "T6001" (polycarbonate diol) manufactured by Asahi Kasei Chemicals Co., Ltd., "C-1090", "C-2090", "C-3090" (polycarbonate diol) manufactured by Kuraray Co., Ltd., etc. As specific examples of polyetheretherketone resins, there can be mentioned "Sumiploy K" manufactured by Sumitomo Chemical Co., Ltd., etc.

[0108] Examples of the polyester resin include polyethylene terephthalate resin, polyethylene naphthalate resin, polybutylene terephthalate resin, polybutylene naphthalate resin, polytrimethylene terephthalate resin, polytrimethylene naphthalate resin, and polycyclohexane dimethyl terephthalate resin.

[0109] From the viewpoint of significantly obtaining the effects of the present invention, the weight average molecular weight (Mw) of the (E) thermoplastic resin is preferably 5,000 or more, more preferably 8,000 or more, further preferably 10,000 or more, particularly preferably 20,000 or more, and is preferably 100,000 or less, more preferably 70,000 or less, further preferably 60,000 or less, and particularly preferably 50,000 or less.

[0110] The content of the (E) thermoplastic resin in the resin composition is not particularly limited. When the total amount of components other than the (B) organic solvent in the resin composition (non-volatile components) is set to 100% by mass, from the viewpoint of significantly obtaining the desired effect of the present invention, it is preferably 20% by mass or less, more preferably 10% by mass or less, further preferably 5% by mass or less, further more preferably 3% by mass or less, and particularly preferably 2% by mass or less. The lower limit may be, for example, 0% by mass or more, 0.01% by mass or more, 0.1% by mass or more, 0.5% by mass or more, or 1% by mass or more.

[0111] The mass ratio of the (E) thermoplastic resin to the (A) epoxy resin in the resin composition ((E) thermoplastic resin / (A) epoxy resin) is not particularly limited, and is, for example, 0 or more, preferably 0.01 or more, more preferably 0.03 or more, and particularly preferably 0.05 or more. The upper limit is not particularly limited, and is preferably 1 or less, more preferably 0.5 or less, and particularly preferably 0.2 or less.

[0112] <(F) Curing accelerator> The resin composition of the present invention may contain (F) a curing accelerator as an optional component. The (F) curing accelerator has a function as a curing catalyst that accelerates the curing of the (A) epoxy resin.

[0113] Examples of the curing accelerator (F) include phosphorus curing accelerators, urea curing accelerators, guanidine curing accelerators, imidazole curing accelerators, metal curing accelerators, and amine curing accelerators. The curing accelerator (F) preferably includes a curing accelerator selected from imidazole curing accelerators and amine curing accelerators. The curing accelerator (F) may be used alone or in combination of two or more.

[0114] Phosphorus curing accelerators include, for example, tetrabutylphosphonium bromide, tetrabutylphosphonium chloride, tetrabutylphosphonium acetate, tetrabutylphosphonium decanoate, tetrabutylphosphonium laurate, bis(tetrabutylphosphonium)pyromellitate, tetrabutylphosphonium hexahydrophthalate, tetrabutylphosphonium 2,6-bis[(2-hydroxy-5-methylphenyl)methyl]-4-methylphenolate, di-tert-butylmethylphosphonium tetraphenylborate and other aliphatic phosphonium salts; methyltriphenylphosphonium bromide, ethyltriphenylphosphonium bromide, propyltriphenylphosphonium bromide, butyltriphenylphosphonium bromide, benzyltriphenylphosphonium chloride, tetraphenylphosphonium bromide, p-tolyltriphenylphosphonium tetraphenylphosphonium; Aromatic phosphonium salts such as p-tolyl borate, tetraphenylphosphonium tetraphenyl borate, tetraphenylphosphonium tetra-p-tolyl borate, triphenylethylphosphonium tetraphenyl borate, tris(3-methylphenyl)ethylphosphonium tetraphenyl borate, tris(2-methoxyphenyl)ethylphosphonium tetraphenyl borate, (4-methylphenyl)triphenylphosphonium thiocyanate, tetraphenylphosphonium thiocyanate, butyltriphenylphosphonium thiocyanate; aromatic phosphine-borane complexes such as triphenylphosphine-triphenylborane; aromatic phosphine-quinone addition reactants such as triphenylphosphine-p-benzoquinone addition reactants; tributylphosphine, tri-tert-butylphosphine, trioctylphosphine, di-tert-butyl(2-butyl)phosphine aliphatic phosphines such as dibutylphenylphosphine, di-tert-butylphenylphosphine, methyldiphenylphosphine, ethyldiphenylphosphine, butyldiphenylphosphine, diphenylcyclohexylphosphine, triphenylphosphine, tri-o-tolylphosphine, tri-m-tolylphosphine, tri-p-tolylphosphine, tri(4-ethylphenyl)phosphine, tri(4-propylphenyl)phosphine, tri(4-isopropylphenyl)phosphine, tri(4-butylphenyl)phosphine, tri(4-tert-butylphenyl)phosphine, tri(2,4-dimethylphenyl)phosphine, tri(2,5-dimethylphenyl)phosphine, tri(2,6-dimethylphenyl)phosphine Aromatic phosphines such as tris(diphenyl)phosphine, tris(3,5-dimethylphenyl)phosphine, tris(2,4,6-trimethylphenyl)phosphine, tris(2,6-dimethyl-4-ethoxyphenyl)phosphine, tris(2-methoxyphenyl)phosphine, tris(4-methoxyphenyl)phosphine, tris(4-ethoxyphenyl)phosphine, tris(4-tert-butoxyphenyl)phosphine, diphenyl-2-pyridylphosphine, 1,2-bis(diphenylphosphino)ethane, 1,3-bis(diphenylphosphino)propane, 1,4-bis(diphenylphosphino)butane, 1,2-bis(diphenylphosphino)acetylene, and 2,2'-bis(diphenylphosphino)diphenyl ether.

[0115] Examples of the urea curing accelerator include 1,1-dimethylurea; aliphatic dimethylureas such as 1,1,3-trimethylurea, 3-ethyl-1,1-dimethylurea, 3-cyclohexyl-1,1-dimethylurea, and 3-cyclooctyl-1,1-dimethylurea; 3-phenyl-1,1-dimethylurea, 3-(4-chlorophenyl)-1,1-dimethylurea, 3-(3,4-dichlorophenyl)-1,1-dimethylurea, 3-(3-chloro-4-methylphenyl)-1,1-dimethylurea, 3-(2-methylphenyl)-1,1-dimethylurea, 3-(4-methylphenyl)-1,1-dimethylurea, 3-(3,4-dimethylphenyl)-1, Aromatic dimethyl urea such as 1-dimethyl urea, 3-(4-isopropylphenyl)-1,1-dimethyl urea, 3-(4-methoxyphenyl)-1,1-dimethyl urea, 3-(4-nitrophenyl)-1,1-dimethyl urea, 3-[4-(4-methoxyphenoxy)phenyl]-1,1-dimethyl urea, 3-[4-(4-chlorophenoxy)phenyl]-1,1-dimethyl urea, 3-[3-(trifluoromethyl)phenyl]-1,1-dimethyl urea, N,N-(1,4-phenylene)bis(N',N'-dimethyl urea), N,N-(4-methyl-1,3-phenylene)bis(N',N'-dimethyl urea) [toluenebisdimethyl urea], and the like.

[0116] Examples of the guanidine curing accelerator include dicyandiamide, 1-methylguanidine, 1-ethylguanidine, 1-cyclohexylguanidine, 1-phenylguanidine, 1-(o-tolyl)guanidine, dimethylguanidine, diphenylguanidine, trimethylguanidine, tetramethylguanidine, pentamethylguanidine, 1,5,7-triazabicyclo[4.4.0]dec-5-ene, 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene, 1-methylbiguanidine, 1-ethylbiguanidine, 1-n-butylbiguanidine, 1-n-octadecylbiguanidine, 1,1-dimethylbiguanidine, 1,1-diethylbiguanidine, 1-cyclohexylbiguanidine, 1-allylbiguanidine, 1-phenylbiguanidine, and 1-(o-tolyl)biguanidine.

[0117] Examples of the imidazole curing accelerator include 2-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, 1-benzyl-2-phenylimidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazole trimellitate, 1-cyanoethyl-2-phenylimidazole trimellitate, 2,4-diamino-6-[2'-methylimidazolyl-(1') imidazole compounds such as 2,4-diamino-6-[2'-undecylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine, 2-phenylimidazole isocyanuric acid adduct, 2-phenyl-4,5-dihydroxymethylimidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole, 2,3-dihydro-1H-pyrrolo[1,2-a]benzimidazole, 1-dodecyl-2-methyl-3-benzylimidazolium chloride, 2-methylimidazoline, and 2-phenylimidazoline, and adducts of imidazole compounds with epoxy resins.

[0118] As the imidazole-based curing accelerator, a commercially available product may be used, and examples thereof include "1B2PZ", "2MZA-PW", "2PHZ-PW", and "C11Z-A" manufactured by Shikoku Chemical Industries, Ltd.; and "P200-H50" manufactured by Mitsubishi Chemical Corporation.

[0119] As metal curing accelerators, for example, organic metal complexes or organic metal salts of metals such as cobalt, copper, zinc, iron, nickel, manganese, and tin can be cited. Specific examples of organic metal complexes include organic cobalt complexes such as cobalt acetylacetonate (II) and cobalt acetylacetonate (III); organic copper complexes such as copper acetylacetonate (II); organic zinc complexes such as zinc acetylacetonate (II); organic iron complexes such as iron acetylacetonate (III); organic nickel complexes such as nickel acetylacetonate (II); organic manganese complexes such as manganese acetylacetonate (II). As organic metal salts, for example, zinc octylate, tin octylate, zinc naphthenate, cobalt naphthenate, tin stearate, zinc stearate, etc. can be cited.

[0120] Examples of the amine-based curing accelerator include trialkylamines such as triethylamine and tributylamine; 4-dimethylaminopyridine, benzyldimethylamine, 2,4,6-tris(dimethylaminomethyl)phenol, and 1,8-diazabicyclo(5,4,0)-undecene.

[0121] As the amine-based curing accelerator, a commercially available product may be used, and examples thereof include "MY-25" manufactured by Ajinomoto Fine-Techno Co., Ltd.

[0122] The content of the (F) curing accelerator in the resin composition is not particularly limited. When the total amount of the components other than the (B) organic solvent in the resin composition (non-volatile components) is set to 100 mass%, the upper limit is preferably 5 mass% or less, more preferably 1 mass% or less, further preferably 0.5 mass% or less, and particularly preferably 0.2 mass% or less. The lower limit can be, for example, 0 mass% or more, 0.001 mass% or more, 0.01 mass% or more, 0.05 mass% or more, etc.

[0123] <(G) Other additives> The resin composition of the present invention may further contain any additives. Examples of such additives include: rubber particles; radical polymerizable compounds having ethylenically unsaturated bonds; radical polymerization initiators such as peroxide-based radical polymerization initiators and azo-based radical polymerization initiators; thermosetting resins other than epoxy resins such as epoxy acrylate resins, polyurethane acrylate resins, polyurethane resins, cyanate resins, benzoxazine resins, unsaturated polyester resins, phenolic resins, melamine resins, and silicone resins; organometallic compounds such as organic copper compounds, organic zinc compounds, and organic cobalt compounds; colorants such as phthalocyanine blue, phthalocyanine green, iodine green, diazo yellow, crystal violet, titanium oxide, and carbon black; polymerization inhibitors such as hydroquinone, catechol, pyrogallol, and phenothiazine; leveling agents such as silicone-based leveling agents and acrylic polymer-based leveling agents; thickeners such as Benton (bentonite) and montmorillonite; silicone-based defoamers, acrylic defoamers, fluorine-based defoamers, and vinyl resin-based defoamers, etc. Defoaming agent; UV absorber such as benzotriazole UV absorber; adhesion enhancer such as urea silane; adhesion imparting agent such as triazole adhesion imparting agent, tetrazole adhesion imparting agent, triazine adhesion imparting agent; antioxidant such as hindered phenol antioxidant; fluorescent brightener such as stilbene derivative; surfactant such as fluorine surfactant and silicone surfactant; flame retardant such as phosphorus flame retardant (such as phosphate compound, phosphazene compound, phosphinic acid compound, red phosphorus), nitrogen flame retardant (such as melamine sulfate), halogen flame retardant, inorganic flame retardant (such as antimony trioxide); dispersant such as phosphate dispersant, polyoxyalkylene dispersant, acetylene dispersant, silicone dispersant, anionic dispersant, cationic dispersant; stabilizer such as borate stabilizer, titanate stabilizer, aluminate stabilizer, zirconate stabilizer, isocyanate stabilizer, carboxylic acid stabilizer, carboxylic anhydride stabilizer, etc. (G) Other additives may be used alone or in combination of two or more at any ratio. A person skilled in the art can appropriately set the content of (G) other additives.

[0124] The content of the radical polymerizable compound is, when the total amount of components other than the (B) organic solvent in the resin composition (non-volatile components) is set to 100 mass %, for example, 0 mass % to 30 mass %, preferably 0 mass % to 10 mass %, more preferably 0 mass % to 5 mass %, further preferably 0 mass % to 2 mass %, further preferably 0 mass % to 1 mass %, and particularly preferably 0 mass % to 0.1 mass %.

[0125] <Method for producing resin composition> The resin composition of the present invention can be produced by appropriately mixing the above-described components and, if necessary, kneading or stirring using a kneading device such as a three-roll mill, a ball mill, a bead mill, a sand mill, or a stirring device such as a super mixer, a planetary mixer, a high-speed rotary mixer, etc.

[0126] <Form of resin composition> The resin composition of the present invention has a viscosity of 3 mPa·s or more, preferably 5 mPa·s or more, more preferably 10 mPa·s or more, further preferably 30 mPa·s or more, particularly preferably 50 mPa·s or more, as measured using an E-type viscometer at 25° C. and 50 rpm, and an upper limit of 5,000 mPa·s or less, preferably 4,000 mPa·s or less, more preferably 3,000 mPa·s or less, further preferably 2,000 mPa·s or less, further more preferably 1,500 mPa·s or less, further preferably 1,000 mPa·s or less, and particularly preferably 800 mPa·s or less.

[0127] The viscosity of the resin composition of the present invention measured using an E-type viscometer at 25° C. and 5 rpm is preferably 3 mPa·s or more, more preferably 5 mPa·s or more, further preferably 10 mPa·s or more, further more preferably 30 mPa·s or more, and particularly preferably 50 mPa·s or more, and the upper limit is preferably 5,000 mPa·s or less, more preferably 4,000 mPa·s or less, further preferably 3,000 mPa·s or less, further more preferably 2,000 mPa·s or less, further preferably 1,500 mPa·s or less, and particularly preferably 1,000 mPa·s or less.

[0128] The resin composition of the present invention has a thixotropic ratio (thixotropic ratio) calculated by dividing the viscosity measured using an E-type viscometer at 25°C and 5 rpm by the viscosity measured using an E-type viscometer at 25°C and 50 rpm, for example, of 1.00 or more, and the upper limit is preferably 3.00 or less, more preferably 2.00 or less, further preferably 1.50 or less, further more preferably 1.30 or less, further preferably 1.20 or less, particularly preferably 1.15 or less, and particularly preferably 1.12 or less.

[0129] <Characteristics of Resin Composition> The resin composition of the present invention comprises (A) an epoxy resin, (B) an organic solvent and (C) an inorganic filler, wherein the content of the organic solvent having a boiling point of less than 100° C. in the component (B) is 5% to 60% by mass when the total amount of the component (B) is set to 100% by mass, and the content of the aromatic solvent in the component (B) is 35% by mass or more when the total amount of the component (B) is set to 100% by mass, and the viscosity of the resin composition measured by an E-type viscometer at 25° C. and 50 rpm is 3mPa·s to 5,000mPa·s. Such a resin composition is difficult to produce resin separation. In addition, by using such a resin composition, nozzle clogging caused by drying of the nozzle can be suppressed, and on the other hand, excellent drying properties after coating can be achieved. In addition, such a resin composition can have excellent thin film forming properties (for example, coating film forming properties with a thickness of less than 50μm). In addition, such a resin composition can suppress poor coating film depression after coating.

[0130] In one embodiment, the cured product (insulating layer) obtained by curing the resin composition of the present invention may have excellent insulation properties. The insulation resistance value of the cured product (insulating layer) obtained by curing the resin composition as measured in the following Test Example 5 is preferably 1.0×10 4 Ω or more, more preferably 1.0×10 6 Ω or more, more preferably 1.0×10 7 Ω or more, more preferably 1.0×10 9 Ω or more, particularly preferably 1.0×10 10 Ω or more.

[0131] <Application of resin composition> The resin composition of the present invention can be suitably used as: a resin composition for forming a coating film on a substrate by roller coating, spray coating, spin coating, bar coating, slit coating, curtain coating or dip coating, and thermally curing the coating film to form an insulating layer (especially the (interlayer) insulating layer of a printed wiring board); preferably a resin composition for forming a coating film on a substrate by slit coating, and thermally curing the coating film to form an insulating layer (especially the (interlayer) insulating layer of a printed wiring board); particularly preferably a resin composition for forming a coating film on a substrate by slit coating, and thermally curing the coating film to form a thin layer (thickness less than 50 μm) of insulating layer (especially the (interlayer) insulating layer of a printed wiring board).

[0132] <Printed wiring board> The printed wiring board of the present invention comprises an insulating layer obtained by curing the resin composition of the present invention.

[0133] A printed wiring board can be produced, for example, by using the resin composition of the present invention and by a method comprising the following steps (1) to (3). (1) Step of applying a resin composition on a substrate to form a coating film (2) Process of drying the coating film (3) A step of thermally curing the coating film to form an insulating layer.

[0134] Step (1) is a step of applying a resin composition on a substrate to form a coating film.

[0135] The "substrate" used in step (I) is a member that becomes the substrate of a printed wiring board, and examples thereof include glass epoxy substrates, metal substrates, polyester substrates, polyimide substrates, BT resin substrates, thermosetting polyphenylene ether substrates, glass substrates, and the like. In addition, the substrate may have a conductor layer on one or both sides thereof, and the conductor layer may also be patterned. An inner substrate having a conductor layer (circuit) formed on one or both sides of the substrate is sometimes referred to as an "inner circuit substrate". In addition, when manufacturing a printed wiring board, an intermediate product to be further formed with an insulating layer and / or a conductor layer is also included in the "substrate" described in the present invention. In the case where the printed wiring board is a circuit board with built-in components, an inner substrate with built-in components can be used.

[0136] The resin composition can be applied to the substrate by, for example, roll coating, spray coating, spin coating, bar coating, slit coating, curtain coating or dip coating. The resin composition of the present invention is preferably applied by slit coating.

[0137] From the viewpoint of thin film formation, the thickness of the coating formed by step (1) is preferably less than 200 μm, more preferably less than 100 μm, further preferably less than 50 μm, further more preferably less than 40 μm, and particularly preferably less than 30 μm. The resin composition of the present invention is particularly useful in forming a film of less than 50 μm using a slit coating method, in which nozzle clogging caused by the drying of the nozzle becomes a significant issue. The lower limit of the thickness of the coating is not particularly limited, for example, it can be more than 0.1 μm, more than 0.5 μm, more than 1 μm, more than 3 μm, more than 5 μm, more than 10 μm, etc.

[0138] Step (2) is a step of drying the coating film. The drying conditions of the resin composition are not particularly limited, and conditions generally used when forming an insulating layer of a printed wiring board can be used.

[0139] The drying of the coating film in step (2) can be carried out, for example, by vacuumization, decompression, heating, hot air blowing, etc., or a combination thereof, preferably by vacuum drying (including decompression drying) and / or heating. By drying the coating film in step (2), the content of the organic solvent in the resin composition is preferably 10% by mass or less, more preferably 5% by mass or less.

[0140] In step (2), when the coating film is vacuum dried, the air pressure is preferably 500 Pa or less, more preferably 200 Pa or less. The vacuum drying time is not particularly limited, but is preferably 30 seconds to 30 minutes, more preferably 30 seconds to 10 minutes.

[0141] In step (2), when the coating film is dried by heating, the heating and drying temperature is preferably 50° C. or higher and lower than 200° C., more preferably 50° C. or higher and lower than 150° C., further preferably 50° C. or higher and lower than 140° C., further more preferably 70° C. or higher and lower than 130° C., and particularly preferably 80° C. or higher and lower than 120° C. The heating and drying time at the heating and drying temperature is preferably 1 minute to 30 minutes, more preferably 1 minute to 10 minutes, and further preferably 1 minute to 5 minutes.

[0142] In the drying of the coating film in step (2), it is particularly preferred to perform vacuum drying before drying by heating. When drying by heating, the viscosity of the coating film decreases as the temperature of the coating film increases, and sometimes the coating film flows and produces unevenness or depressions. However, in the case of vacuum drying, heating is not performed, but the temperature of the coating film decreases and the viscosity increases due to evaporation heat, thereby suppressing the flow of the coating film.

[0143] Step (3) is a step of thermally curing the coating film to form an insulating layer. The thermal curing conditions of the resin composition are not particularly limited, and conditions generally used when forming an insulating layer of a printed wiring board can be used.

[0144] The heat curing conditions of the resin composition vary depending on the types of components contained in the resin composition, and in one embodiment, the curing temperature is preferably 150° C. to 240° C., more preferably 160° C. to 220° C., and even more preferably 170° C. to 210° C. The curing time for maintaining the above curing temperature may be preferably 30 minutes to 300 minutes, more preferably 60 minutes to 240 minutes, and even more preferably 90 minutes to 180 minutes.

[0145] The thickness of the insulating layer formed by step (3) is preferably 200 μm or less, more preferably 100 μm or less, further preferably 50 μm or less, further more preferably 40 μm or less, and particularly preferably 30 μm or less. The lower limit of the thickness of the insulating layer is not particularly limited, and for example, it may be 0.1 μm or more, 0.5 μm or more, 1 μm or more, 3 μm or more, 5 μm or more, 10 μm or more, etc.

[0146] When manufacturing a printed wiring board, in addition to the above steps (1) to (3), a step (4) of opening holes in the insulating layer, a step (5) of roughening the insulating layer, and a step (6) of forming a conductor layer may be further performed. These steps (4) to (6) may be performed according to various methods known to those skilled in the art used in the manufacture of printed wiring boards. In addition, as required, the formation of the insulating layer and the conductor layer in steps (1) to (6) may be repeated to form a multilayer wiring board.

[0147] Step (4) is a step of drilling holes in the insulating layer, thereby forming holes such as through holes and vias in the insulating layer. Step (4) can be performed using, for example, a drill, laser, plasma, etc., depending on the composition of the resin composition used in forming the insulating layer. The size and shape of the hole can be appropriately determined according to the design of the printed wiring board.

[0148] Step (5) is a step of roughening the insulating layer. Usually, in step (5), contamination is also removed. The order and conditions of the roughening treatment are not particularly limited, and the known order and conditions commonly used when forming the insulating layer of the printed wiring board can be adopted. For example, the insulating layer can be roughened by swelling treatment with a swelling solution, roughening treatment with an oxidant, and neutralization treatment with a neutralizing solution in sequence.

[0149] The swelling liquid used in the roughening treatment is not particularly limited, and examples thereof include alkaline solutions, surfactant solutions, and the like. Alkaline solutions are preferred, and sodium hydroxide solutions and potassium hydroxide solutions are more preferred as the alkaline solutions. Examples of commercially available swelling liquids include, for example, "Swelling Dip Securiganth P" and "Swelling Dip Securiganth SBU" manufactured by Atotech Japan Co., Ltd. The swelling treatment using the swelling liquid is not particularly limited, and for example, it can be performed by immersing the insulating layer in a swelling liquid at 30°C to 90°C for 1 minute to 20 minutes. From the viewpoint of controlling the swelling of the resin of the insulating layer to an appropriate level, it is preferred that the insulating layer be immersed in a swelling liquid at 40°C to 80°C for 5 minutes to 15 minutes.

[0150] The oxidant used in the roughening treatment is not particularly limited, and an alkaline permanganate solution in which potassium permanganate or sodium permanganate is dissolved in an aqueous solution of sodium hydroxide can be cited, for example. The roughening treatment using an oxidant such as an alkaline permanganate solution is preferably performed by immersing the insulating layer in an oxidant solution heated to 60°C to 100°C for 10 minutes to 30 minutes. In addition, the concentration of permanganate in the alkaline permanganate solution is preferably 5% to 10% by mass. As commercially available oxidants, alkaline permanganate solutions such as "Concentrate Compact CP" and "Dosing solution Securiganth P" manufactured by Atotech Japan can be cited.

[0151] The neutralizing solution used in the roughening treatment is preferably an acidic aqueous solution, and examples of commercially available products include "Reduction solution Securiganth P" manufactured by Atotech Japan Co., Ltd.

[0152] The treatment with the neutralizing solution can be performed by immersing the surface roughened with the oxidizing agent in the neutralizing solution at 30° C. to 80° C. for 5 to 30 minutes. In view of operability, it is preferred to immerse the object roughened with the oxidizing agent in the neutralizing solution at 40° C. to 70° C. for 5 to 20 minutes.

[0153] In one embodiment, the arithmetic mean roughness (Ra) of the insulating layer surface after roughening treatment is not particularly limited, but is preferably less than 500nm, more preferably less than 400nm, and more preferably less than 300nm. There is no particular limitation on the lower limit, for example, it can be more than 1nm, more than 2nm, etc. In addition, the root mean square roughness (Rq) of the insulating layer surface after roughening treatment is preferably less than 500nm, more preferably less than 400nm, and more preferably less than 300nm. There is no particular limitation on the lower limit, for example, it can be more than 1nm, more than 2nm, etc. The arithmetic mean roughness (Ra) and root mean square roughness (Rq) of the insulating layer surface can be measured using a non-contact surface roughness meter.

[0154] Step (6) is a step of forming a conductor layer, and a conductor layer is formed on the insulating layer. The conductor material used in the conductor layer is not particularly limited. In a preferred embodiment, the conductor layer comprises one or more metals selected from gold, platinum, palladium, silver, copper, aluminum, cobalt, chromium, zinc, nickel, titanium, tungsten, iron, tin and indium. The conductor layer may be a single metal layer or an alloy layer. As the alloy layer, for example, a layer formed by an alloy of two or more metals selected from the above metals (e.g., nickel-chromium alloy, copper-nickel alloy and copper-titanium alloy) can be cited. Among them, from the viewpoints of versatility, cost, ease of patterning, etc. in forming the conductor layer, a single metal layer of chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver or copper, or an alloy layer of nickel-chromium alloy, copper-nickel alloy or copper-titanium alloy is preferred, a single metal layer of chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver or copper, or an alloy layer of nickel-chromium alloy is more preferred, and a single metal layer of copper is further preferred.

[0155] The conductor layer may be a single-layer structure or a multilayer structure in which two or more single metal layers or alloy layers formed of different types of metals or alloys are stacked. When the conductor layer is a multilayer structure, the layer in contact with the insulating layer is preferably a single metal layer of chromium, zinc or titanium or an alloy layer of a nickel-chromium alloy.

[0156] The thickness of the conductor layer varies depending on the desired design of the printed wiring board, but is generally 3 μm to 35 μm, preferably 5 μm to 30 μm.

[0157] In one embodiment, the conductor layer can be formed by plating. For example, the surface of the insulating layer can be plated by a conventionally known technique such as a semi-additive method or a full-additive method to form a conductor layer having a desired wiring pattern. From the perspective of manufacturing simplicity, it is preferably formed by a semi-additive method. An example of forming a conductor layer by a semi-additive method is shown below.

[0158] First, a plating seed layer is formed on the surface of the insulating layer by electroless plating. Next, a mask pattern is formed on the formed plating seed layer to expose a portion of the plating seed layer corresponding to the desired wiring pattern. After a metal layer is formed on the exposed plating seed layer by electrolytic plating, the mask pattern is removed. Then, the unnecessary plating seed layer is removed by etching or the like, thereby forming a conductor layer having a desired wiring pattern.

[0159] <Semiconductor Device> The printed wiring board described above can be used for a semiconductor device including the printed wiring board.

[0160] Examples of the semiconductor device include various semiconductor devices used in electrical products (eg, computers, mobile phones, digital cameras, and televisions) and vehicles (eg, motorcycles, cars, trains, ships, and airplanes). Example

[0161] The present invention is specifically described below by way of examples. The present invention is not limited to these examples. It should be noted that, below, "parts" and "%" indicating amounts refer to "parts by mass" and "% by mass" respectively unless otherwise indicated. The temperature conditions and pressure conditions when the temperature and pressure are not particularly specified are room temperature (25°C) and normal pressure (1 atm), respectively.

[0162] <Example 1> 43 parts of biphenyl epoxy resin ("NC-3000L" manufactured by Nippon Kayaku Co., Ltd.), 28 parts of bisphenol epoxy resin ("ZX1059" manufactured by Nippon Steel Chemical Materials Co., Ltd.), 10 parts of aminotriazine skeleton cresol novolac resin ("LA-3018-50P" manufactured by DIC Corporation, a PGM (propylene glycol monomethyl ether (also known as 1-methoxy-2-propanol)) solution having a solid content of 50% by mass), 45 parts of active ester curing agent ("HPC-8000-65T" manufactured by DIC Corporation, a toluene solution having a solid content of 65% by mass), phenoxy resin ("YX7553BH30" manufactured by Mitsubishi Chemical Corporation, anone (cyclohexanone) / MEK having a solid content of 30% by mass) were mixed. The resin composition is prepared by mixing 26 parts of methyl ethyl ketone (1:1 solution), 26 parts of spherical silica (100 parts of "SOC2" manufactured by Yaduma Co., Ltd. and 0.6 parts of aminosilane coupling agent ("KBM-573" manufactured by Shin-Etsu Chemical Co., Ltd., N-phenyl-3-aminopropyltrimethoxysilane) surface-treated spherical silica, with an average particle size of 0.5 μm), 0.5 parts of 4-dimethylaminopyridine ("DMAP" manufactured by Tokyo Chemical Industry Co., Ltd.), 50 parts of MEK (methyl ethyl ketone), and 360 parts of an aromatic high-boiling point solvent ("Ipzole 150" manufactured by Idemitsu Kosan Co., Ltd., with an initial boiling point of 184°C and a dry point of 205°C), and stirring at room temperature until a uniform solution is formed to obtain a varnish-like resin composition.

[0163] <Example 2> A varnish-like resin composition was obtained in the same manner as in Example 1 except that the amount of the aromatic high-boiling-point solvent ("Ipzole 150" manufactured by Idemitsu Kosan Co., Ltd.) used was changed from 360 parts to 160 parts.

[0164] <Example 3> A varnish-like resin composition was obtained in the same manner as in Example 1 except that the amount of the aromatic high-boiling-point solvent ("Ipzole 150" manufactured by Idemitsu Kosan Co., Ltd.) used was changed from 360 parts to 25 parts.

[0165] <Example 4> A varnish-like resin composition was obtained in the same manner as in Example 1, except that 43 parts of a dicyclopentadiene epoxy resin ("HP7200" manufactured by DIC Corporation) was used instead of 43 parts of a biphenyl epoxy resin ("NC-3000L" manufactured by Nippon Kayaku Co., Ltd.) and the amount of an aromatic high-boiling point solvent ("Ipzole150" manufactured by Idemitsu Kosan Co., Ltd.) was changed from 360 parts to 160 parts.

[0166] <Example 5> A varnish-like resin composition was obtained in the same manner as in Example 1 except that 20 parts of MEK (methyl ethyl ketone) was additionally used and the amount of the aromatic high-boiling point solvent ("Ipzole 150" manufactured by Idemitsu Kosan Co., Ltd.) used was changed from 360 parts to 50 parts.

[0167] <Example 6> A varnish-like resin composition was obtained in the same manner as in Example 1 except that 40 parts of MEK (methyl ethyl ketone) was additionally used and the amount of the aromatic high-boiling-point solvent ("Ipzole 150" manufactured by Idemitsu Kosan Co., Ltd.) used was changed from 360 parts to 50 parts.

[0168] <Example 7> A varnish-like resin composition was obtained in the same manner as in Example 1 except that 45 parts of active ester curing agent ("HPC-8000-65T" manufactured by DIC Corporation, a toluene solution having a solid content of 65% by mass) was not used.

[0169] <Example 8> A varnish-like resin composition was obtained in the same manner as in Example 1, except that the amount of the aromatic high-boiling-point solvent ("Ipzole 150" manufactured by Idemitsu Kosan Co., Ltd.) used was changed from 360 parts to 160 parts, and 45 parts of the active ester curing agent ("HPC-8000-65T" manufactured by DIC Corporation, a toluene solution having a solid content of 65% by mass) was not used.

[0170] <Example 9> A varnish-like resin composition was obtained in the same manner as in Example 1, except that the amount of the aromatic high-boiling-point solvent ("Ipzole 150" manufactured by Idemitsu Kosan Co., Ltd.) used was changed from 360 parts to 40 parts, and 45 parts of the active ester curing agent ("HPC-8000-65T" manufactured by DIC Corporation, a toluene solution having a solid content of 65% by mass) was not used.

[0171] <Comparative Example 1> A varnish-like resin composition was obtained in the same manner as in Example 1 except that 50 parts of MEK (methyl ethyl ketone) was additionally used and the amount of the aromatic high-boiling-point solvent ("Ipzole 150" manufactured by Idemitsu Kosan Co., Ltd.) used was changed from 360 parts to 30 parts.

[0172] <Comparative Example 2> A varnish-like resin composition was obtained in the same manner as in Example 1 except that 160 parts of Anone (cyclohexanone) was additionally used and 360 parts of an aromatic high-boiling-point solvent ("Ipzole 150" manufactured by Idemitsu Kosan Co., Ltd.) was not used.

[0173] <Comparative Example 3> A varnish-like resin composition was obtained in the same manner as in Example 1 except that 160 parts of NMP (N-methyl-2-pyrrolidone) was additionally used and 360 parts of an aromatic high-boiling-point solvent ("Ipzole 150" manufactured by Idemitsu Kosan Co., Ltd.) was not used.

[0174] <Comparative Example 4> A varnish-like resin composition was obtained in the same manner as in Example 1 except that 160 parts of GBL (γ-butyrolactone) was additionally used and 360 parts of an aromatic high-boiling-point solvent (“Ipzole 150” manufactured by Idemitsu Kosan Co., Ltd.) was not used.

[0175] <Comparative Example 5> A varnish-like resin composition was obtained in the same manner as in Example 1 except that the amount of the aromatic high-boiling-point solvent ("Ipzole 150" manufactured by Idemitsu Kosan Co., Ltd.) used was changed from 360 parts to 500 parts.

[0176] <Comparative Example 6> A varnish-like resin composition was obtained in the same manner as in Example 1 except that the amount of the aromatic high-boiling-point solvent ("Ipzole 150" manufactured by Idemitsu Kosan Co., Ltd.) used was changed from 360 parts to 25 parts and 50 parts of MEK (methyl ethyl ketone) was not used.

[0177] <Test Example 1: Evaluation of Suppression of Nozzle Clogging Due to Nozzle Drying> The varnish-like resin composition obtained in the above-mentioned embodiment or comparative example was put into a slit coater (manufactured by Kondo Corporation), and one slit coating was applied on a glass plate to a film thickness of 25 μm. After the slit coating was applied, the slit coating was applied again after standing for 20 minutes. The situation in which a uniform coating film could be formed at this time was evaluated as “○”, and the situation in which a uniform coating film could not be formed due to nozzle clogging was evaluated as “×”.

[0178] <Test Example 2: Evaluation of Drying Properties after Coating> The varnish-like resin composition obtained in the above-mentioned embodiment or comparative example was put into a slit coater (manufactured by Kondo Co., Ltd.), and one slit coating was applied on a glass plate to a film thickness of 25 μm. The glass plate formed with the coating film by slit coating was vacuum dried for 1 minute, dried on a hot plate at 100° C. for 3 minutes, and a PET film was placed on the coating film and left at room temperature for 30 minutes. The situation where the coating film after placement was not in close contact with the PET film was evaluated as “○”, and the situation where it was in close contact was evaluated as “×”.

[0179] <Test Example 3: Evaluation of coating film depression after coating> The varnish-like resin composition obtained in the above-mentioned embodiment or comparative example is put into a slit coater (manufactured by Kondo Co.), and one slit coating is applied on a glass plate to make the film thickness 25 μm. After the glass plate with the coating formed by slit coating is vacuum dried for 1 minute, it is dried on a hot plate at 100°C for 3 minutes, and then heated in an oven at 180°C for 40 minutes. When measuring the thickness of the entire substrate obtained, the case where the difference in thickness is less than 5 μm is evaluated as "○", and the case where the difference in thickness is more than 5 μm is evaluated as "×". It should be noted that the difference in thickness here includes the deviation (X direction) of the coating starting point, the middle point, and the end point, and the deviation (Y direction) of the left and right center of the coater, and both are measured and determined.

[0180] <Test Example 4: Evaluation of Thin Film Formability> In the measurement of the thickness of the entire substrate in Test Example 3, the case where the average film thickness was 25 μm±2 μm was evaluated as “○”, and the case where it was not 25 μm±2 μm was evaluated as “×”.

[0181] <Test Example 5: Insulation Resistance Test> The varnish-like resin composition obtained in the above-mentioned embodiment or comparative example is put into a slit coater (manufactured by Kondo Co., Ltd.), and slit coating is performed on the copper-clad laminate to make the film thickness 25 μm. The obtained sample is vacuum dried for 1 minute and then dried on a hot plate at 100°C for 3 minutes. A copper foil is placed on the coating film of the dried sample, and after laminating the copper foil using a vacuum laminator, it is heated in an oven at 180°C for 40 minutes, and then heated in an oven at 200°C for 120 minutes to completely cure the coating film. A voltage of 5 V is applied between the copper-clad laminate and the copper foil of the obtained sample to measure the insulation resistance value. The insulation resistance value is set to 1.0×10 7 The case with a value of Ω or more was evaluated as "○", and the case with a value less than 1.0×10 7 The case of Ω was evaluated as "×".

[0182] <Test Example 6: Measurement of Viscosity and Calculation of Thixotropic Ratio> The viscosity of the varnish-like resin composition was measured for 2 minutes using an E-type viscometer ("RE80 Viscometer" manufactured by Toki Sangyo Co., Ltd.) at a measurement temperature of 25°C, a rotor of 1.34°×R24, an amount of the varnish-like resin composition of 1.2 ml, and a rotation speed of 5 rpm and 50 rpm. Furthermore, the thixotropic ratio was calculated by dividing the viscosity measured at 5 rpm by the viscosity measured at 50 rpm.

[0183] <Test Example 7: Evaluation of poor resin separation> The varnish-like resin composition obtained in the above-mentioned Examples or Comparative Examples was stored at -40°C for 1 week and then left to stand at room temperature of 25°C until the temperature of the resin composition reached 25°C. A prepared slide of the resin composition at 25°C was prepared using a slide glass and a cover glass, and observed under an optical microscope to confirm the presence or absence of poor separation of the resin.

[0184] The occurrence of resin separation of about 100 μm was observed at a magnification of 50 times, and the occurrence of resin separation of about 10 μm was observed at a magnification of 500 times. The case where there was no resin separation was judged as "○", and the case where either or both sides had resin separation was judged as "×".

[0185] <Example 10> Using the varnish-like resin composition obtained in Example 2, evaluation was performed in the same manner as in Test Examples 1 to 7, except that vacuum drying was not performed in Test Examples 2 to 5.

[0186] <Example 11> Evaluation was performed in the same manner as in Test Examples 1 to 7, using the varnish-like resin composition obtained in Example 2, except that the glass plate in Test Examples 1 to 4 was changed to a glass epoxy substrate.

[0187] The content of each component of the resin composition obtained in the Examples and Comparative Examples, and the measurement results and evaluation results of the Test Examples are shown in Table 1 below.

[0188] [Table 1]

[0189] As shown in Table 1, it can be seen that the following resin composition can suppress poor resin separation associated with low solubility of the resin and can suppress nozzle clogging caused by drying of the nozzle. On the other hand, it can suppress poor coating film depression after coating and has excellent film formability; the resin composition comprises (A) an epoxy resin, (B) an organic solvent and (C) an inorganic filler, the content of the organic solvent having a boiling point of less than 100° C. in the component (B) is 5% to 60% by mass when the total amount of the component (B) (total (B) components) is 100% by mass, the content of the aromatic solvent in the component (B) is 35% by mass or more when the total amount of the component (B) is 100% by mass, and the viscosity of the resin composition measured by an E-type viscometer at 25° C. and 50 rpm is 3 mPa·s to 5,000 mPa·s.

Claims

1. A resin composition comprising (A) an epoxy resin, (B) an organic solvent and (C) an inorganic filler, wherein: When the total amount of the component (B) is 100% by mass, the content of the organic solvent having a boiling point of less than 100° C. in the component (B) is 5% by mass to 60% by mass. When the total amount of component (B) is set to 100% by mass, the content of the aromatic solvent in component (B) is 35% by mass or more, the viscosity of the resin composition measured using an E-type viscometer at 25°C and 50 rpm is 3mPa·s to 5,000mPa·s, and the resin composition is used to form a coating film by coating on a substrate by roller coating, spray coating, spin coating, blade coating, slit coating, curtain coating or dip coating, and the coating film is thermally cured to form an insulating layer.

2. The resin composition according to claim 1, wherein The resin composition is applied on a substrate by a slit coating method to form a coating film, and the coating film is thermally cured to form an insulating layer.

3. The resin composition according to claim 1, wherein When the total amount of components other than the component (B) in the resin composition is 100% by mass, the content of the component (C) is 85% by mass or less.

4. The resin composition according to claim 1, wherein When the total amount of components other than the component (B) in the resin composition is 100% by mass, the content of the component (C) is 60% by mass or more.

5. The resin composition according to claim 1, wherein When the total amount of the component (B) is 100% by mass, the content of the aromatic solvent in the component (B) is 85% by mass or less.

6. The resin composition according to claim 1, wherein When the total amount of the component (B) is 100% by mass, the content of the organic solvent having a boiling point of 130° C. or higher in the component (B) is 25% by mass to 90% by mass.

7. The resin composition according to claim 1, wherein When the total amount of the component (B) is 100% by mass, the content of the organic solvent having a boiling point of 100° C. or higher and lower than 130° C. in the component (B) is 1% by mass to 20% by mass.

8. The resin composition according to claim 1, wherein When the total amount of the component (B) is 100% by mass, the content of the organic solvent having a boiling point of 100° C. or higher and lower than 130° C. in the component (B) is 5% by mass or more.

9. The resin composition according to claim 1, wherein When the total amount of the component (B) is 100% by mass, the content of the non-aromatic solvent having a boiling point of 130° C. or higher in the component (B) is 10% by mass or less.

10. The resin composition according to claim 1, wherein When the total amount of the component (B) is 100% by mass, the content of the aromatic solvent having a boiling point of 130° C. or higher in the component (B) is 20% by mass or more.

11. The resin composition according to claim 1, wherein When the total amount of the aromatic solvent is 100% by mass, the content of the aromatic solvent having a boiling point of 130° C. or higher in the aromatic solvent is 60% by mass or more.

12. The resin composition according to claim 1, wherein The component (B) comprises a C9 aromatic hydrocarbon and a C 10 Aromatic solvents among aromatic hydrocarbons.

13. The resin composition according to claim 1, wherein When the total amount of the component (B) is 100% by mass, the content of the organic solvent consisting of constituent atoms selected from carbon atoms, oxygen atoms and hydrogen atoms in the organic solvent (B) is 98% by mass or more.

14. The resin composition according to claim 1, wherein When all the components in the resin composition are defined as 100% by mass, the content of the component (B) is 15% by mass to 50% by mass.

15. The resin composition according to claim 1, wherein When the total amount of components other than the component (B) in the resin composition is 100% by mass, the content of the radical polymerizable compound is 0% by mass to 2% by mass.

16. The resin composition according to claim 1, wherein The viscosity measured using an E-type viscometer at 25° C. and 50 rpm is 50 mPa·s to 1,500 mPa·s.

17. The resin composition according to claim 1, wherein The thixotropic ratio calculated by dividing the viscosity measured at 25° C. and 5 rpm using an E-type viscometer by the viscosity measured at 25° C. and 50 rpm using an E-type viscometer is 1.00 to 1.

50.

18. The resin composition according to claim 1, wherein The thixotropic ratio calculated by dividing the viscosity measured at 25° C. and 5 rpm using an E-type viscometer by the viscosity measured at 25° C. and 50 rpm using an E-type viscometer is 1.00 to 1.

15.

19. A printed wiring board, wherein: An insulating layer is provided which is formed of a cured product of the resin composition according to any one of claims 1 to 18.

20. A semiconductor device, wherein: A printed wiring board comprising the method according to claim 19.

21. A method for producing a printed wiring board, wherein the method uses a resin composition having the following characteristics: comprising (A) epoxy resin, (B) organic solvent and (C) inorganic filler material, When the total amount of the component (B) is 100% by mass, the content of the organic solvent having a boiling point of less than 100° C. in the component (B) is 5% by mass to 60% by mass. When the total amount of component (B) is 100% by mass, the content of the aromatic solvent in component (B) is 35% by mass or more, and the viscosity measured using an E-type viscometer at 25° C. and 50 rpm is 3 mPa·s to 5,000 mPa·s; The method for manufacturing the printed wiring board comprises the following steps (1) to (3): (1) A step of applying the resin composition onto a substrate by a slit coating method to form a coating film (2) A step of vacuum drying the coating film and / or drying the coating film at a temperature of 50° C. or higher and less than 150° C. (3) A step of thermally curing the coating film at a temperature of 150° C. to 240° C. to form an insulating layer.